Water dispersion of vinylidene chloride copolymer, film, and paper laminate
A vinylidene chloride copolymer film with controlled haze and additives addresses yellowing issues, ensuring high water vapor barrier and appearance stability for packaging applications.
Patent Information
- Application Number
- JP2023115514
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-24
AI Technical Summary
Vinylidene chloride copolymers used in packaging films tend to yellow over time, compromising their appearance and suitability for food and pharmaceutical packaging, despite having high gas barrier properties.
A vinylidene chloride copolymer-based film with a specific composition and structure, characterized by a high molecular compound ratio, controlled haze, and inclusion of additives to suppress yellowing while maintaining high water vapor barrier properties.
The film maintains a high water vapor barrier while significantly reducing yellowing, making it suitable for long-term use in packaging without compromising the appearance.
Smart Images

Figure 2025012586000001 
Figure 2025012586000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous dispersion of a vinylidene chloride copolymer, and to films and paper laminates having a layer coated with the aqueous dispersion of a vinylidene chloride copolymer. [Background technology]
[0002] In order to maintain the quality of food and medicine, the film used to package them must adequately block and seal gases in the atmosphere, such as oxygen, nitrogen, carbon dioxide, and water vapor. In this regard, among various resins, a film having a layer formed from an aqueous dispersion of a vinyl halide copolymer, particularly an aqueous dispersion of a vinylidene chloride copolymer, has excellent barrier properties against water vapor and oxygen, and is therefore very suitable for food and medicine packaging applications.
[0003] In recent years, packaging films are required to have higher gas barrier properties for the following reasons. 1) Maintaining the quality and efficacy of medicines and food ingredients for a longer period of time; 2) Thinner film to meet the demand for improved extrusion of contents in packaging products due to the aging population; 3) Thinner film to improve productivity. As aqueous dispersions of vinylidene chloride copolymers constituting a film having barrier properties, those described in Patent Documents 1 to 5, for example, are known. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-100551 A [Patent Document 2] JP 2023-506844 A [Patent Document 3] JP 2022-117395 A [Patent Document 4] Japanese Patent Application Publication No. 3-33147 [Patent Document 5] Japanese Patent Application Publication No. 1-113242 Summary of the Invention [Problem to be solved by the invention]
[0005] The vinylidene chloride copolymers described in Patent Documents 1 to 5 have a problem that they turn yellow over time while stored as a film, that is, their appearance gradually deteriorates. In particular, the vinylidene chloride copolymer described in Patent Document 2 has higher gas barrier properties than those described in Patent Documents 1 and 3 to 5, but there is room for further improvement in terms of yellowing. This is because the comonomers that increase the gas barrier properties also have the property of increasing yellowing, and there is a trade-off between gas barrier properties and yellowing resistance. In addition, although films are usually used in units of one sheet, the color of the film in the wound roll state is also an important physical property. Films that are strongly yellowish in the roll state are not preferred by pharmaceutical and food manufacturers who use them. This is because the yellowish color of the film may be mistaken by general consumers as deterioration of the product itself. In this context, there is a market need for an aqueous dispersion of vinylidene chloride copolymer that can form a film with little yellowish color in the roll state.
[0006] Therefore, an object of the present invention is to provide an aqueous dispersion of a vinylidene chloride copolymer capable of forming a coating film in which yellowing is suppressed in a rolled state while maintaining high water vapor barrier properties. Another object of the present invention is to provide a film and a paper laminate having a vinylidene chloride copolymer layer in which yellowing is suppressed in a rolled state while maintaining high water vapor barrier properties. [Means for solving the problem]
[0007] That is, the present invention is as follows. [1] When the coating is applied, the coating is 50 g / m 2 The water vapor transmission rate per unit area is 0.8g / (m2) at 38℃ and 90% Rh. 2 ·day) or less, and the coating film is 50 g / m 2The aqueous dispersion of a vinylidene chloride copolymer is characterized in that the haze per unit area is more than 2.2%. [2] The aqueous dispersion of the vinylidene chloride copolymer according to [1], having a solid content of 50% by mass or more. [3] Contains polymer compounds other than vinylidene chloride copolymers, The aqueous dispersion of a vinylidene chloride copolymer according to [1] or [2], wherein the total mass ratio of the polymer compound and a vinylidene chloride copolymer in which a proportion of structural units derived from vinylidene chloride is more than 0 mass% and not more than 70 mass% is more than 0 mass% and not more than 15 mass%, when the dry mass of the aqueous dispersion of the vinylidene chloride copolymer is taken as 100 mass%. [4] the vinylidene chloride copolymer contains 1.0 to 20 mass % of structural units derived from a monomer having a reactivity ratio r1 with vinylidene chloride of less than 0.7; The aqueous dispersion of a vinylidene chloride copolymer according to any one of [1] to [3], wherein the copolymerization monomer having a reactivity ratio r1 of less than 0.7 is at least one selected from the group consisting of methyl methacrylate, acrylonitrile, methacrylonitrile, acrylic acid, itaconic acid, maleic acid, and methacrylic acid. [5] The aqueous dispersion according to [4], wherein the vinylidene chloride copolymer contains 1.0 to 15 mass % of structural units derived from methacrylonitrile when the vinylidene chloride copolymer is taken as 100 mass %. [6] A film or paper laminate comprising a vinylidene chloride copolymer layer formed by coating an aqueous dispersion of the vinylidene chloride copolymer according to any one of [1] to [5]. [7] A blister packaging film having a vinylidene chloride copolymer layer formed by applying an aqueous dispersion of a vinylidene chloride copolymer, Water vapor permeability is 0.4g / (m at 38℃ and 90% Rh. 2 ·day) or less, Haze is 3.0% or more, The vinylidene chloride copolymer contains 1.0 to 15 mass % of structural units derived from methacrylonitrile. A blister packaging film comprising: Effect of the Invention
[0008] According to the present invention, it is possible to provide an aqueous dispersion of a vinylidene chloride copolymer capable of forming a coating film in which yellowing is suppressed in a rolled state while maintaining high water vapor barrier properties. Also, according to the present invention, it is possible to provide a film and a paper laminate having a vinylidene chloride copolymer in which yellowing is suppressed in a rolled state while maintaining high water vapor barrier properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment for carrying out the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. The following embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out by appropriately modifying it within the scope of its gist.
[0010] [Water dispersion of vinylidene chloride copolymer] The aqueous dispersion of the vinylidene chloride copolymer of this embodiment (hereinafter also simply referred to as "aqueous dispersion") has a form in which particles of the vinylidene chloride copolymer are dispersed in an aqueous solvent. The content of the organic solvent contained in the aqueous solvent is preferably 5 parts by mass or less, more preferably less than 1 part by mass, and particularly preferably 0 part by mass, when the mass of water is 100 parts by mass. The inclusion of an organic solvent is undesirable from the viewpoints of the working environment, environmental load, equipment deterioration, and flammability of the solvent. The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment has a coating film thickness of 50 g / m 2 The water vapor transmission rate per unit area is 0.8g / (m2) at 38℃ and 90% Rh. 2 ·day) and less than 50g / m 2 It is characterized by a haze of more than 2.2% per unit area.
[0011] Coating film 50g / m2 The water vapor transmission rate (38℃, 90% Rh) is 0.7g / (m 2 ·day), and more preferably 0.5 g / (m 2 ·day), and more preferably 0.4 g / (m 2 ·day), and particularly preferably 0.35 g / (m 2 ·day) Coating film 50g / m 2 By designing the water vapor transmission rate per unit area to be within this range, a film having a vinylidene chloride copolymer layer formed by applying an aqueous dispersion thereto can sufficiently protect the contents from water vapor with a vinylidene chloride copolymer layer having a small thickness. The lower limit of the water vapor transmission rate is not particularly limited, and may be, for example, 0 g / (m 2 ·day) or more, and 2 ·day) or more, and 2 10 days) or more.
[0012] Coating film 50g / m 2 The water vapor transmission rate per unit is 50g / m 2 The measurement can be performed by preparing a standard coated film of the above formula. The method for preparing the standard coated film is as follows. <50g / m 2 How to make standard coated film> A water dispersion was applied to a polyethylene terephthalate (PET) film (haze 2.0% or less) with a thickness of 12 μm at a dry weight of 10 g / m 2 Apply the paint with a wire bar so that the paint is 50 g / m2 and then dry it in an oven heated to 80°C for 1 minute. Repeat this process 5 times to achieve a paint thickness of 50 g / m2. 2 A standard coated film of In the process of overcoating, if coating defects such as repellency, cracks, bar streaks, blisters, poor drying, etc. occur, excellent water vapor barrier properties are usually not achieved. In this respect, the aqueous dispersion is required to have overcoating suitability that allows overcoating to be performed without defects.
[0013] <50g / m 2 How to measure water vapor transmission rate per unit area> Above <50g / m 2 The standard coated film prepared by the method for preparing a standard coated film in is stored in an oven at 40°C for two days, and then the water vapor transmission rate is measured at 38°C and 90% RH using a water vapor transmission rate measuring device (e.g., Mocon's "PERMATRAN W-3 / 34G"). The average value of the measurements taken between 48 and 60 hours after the start of the measurement is regarded as the water vapor transmission rate. The measurement is carried out four times, and the average value is regarded as the water vapor transmission rate of the standard coated film. In addition, since the water vapor permeability of a PET film is higher than that of a vinylidene chloride copolymer layer formed by coating an aqueous dispersion, there is no problem in using the water vapor permeability of a standard coated film as the water vapor permeability of the coating film (vinylidene chloride copolymer layer) of the aqueous dispersion.
[0014] Generally, the water vapor transmission rate P of a multilayer film is expressed by the following relational expression (1). L / P = Σ(l i / p i ) ···(1) (wherein i is the layer number, L is the total thickness of the multilayer film, and l i is the thickness of the i-th layer, p i is the water vapor transmission rate of the i-th layer) Thus, for example, the following <10 g / m 2 10g / m2 produced by the standard coating film production method 2 Standard coated film, etc., above <50g / m 2 From films made by methods other than the standard coating film manufacturing method of 50 g / m 2 The water vapor transmission rate per unit area can be estimated using the above formula (1). <10g / m 2 How to make standard coated film> A 10 g / m2 aqueous dispersion was applied to a 12 μm thick PET film (haze 2.0% or less) at a dry weight. 2 Then, dry it for 1 minute in an oven heated to 80°C and apply a 10g / m 2 A standard coated film of
[0015] Coating film 50g / m 2 Examples of methods for controlling the water vapor transmission rate per unit area within the above range include, as described below, a method for adjusting the content of structural units derived from vinylidene chloride in the vinylidene chloride copolymer, a method for reducing the water vapor transmission rate by adding a crystal nucleating agent, and a method for adjusting the mass proportion of a copolymerization monomer having a reactivity ratio r1 to vinylidene chloride of less than 0.7 in the vinylidene chloride copolymer.
[0016] Discoloration of a film having a vinylidene chloride copolymer layer formed by coating an aqueous dispersion is often evaluated using a color difference meter with only one film or with multiple films stacked together. The color measured by this method does not necessarily correlate with the color in a rolled state. This is because the optical path length is different. An example will be given below. Assuming that there is a vinylidene chloride copolymer coating film with a length of 30 cm, a width of 10 cm, and a thickness of 30 μm, when this coating film is viewed from directly above (from the thickness direction), the optical path length is 30 μm, which corresponds to the thickness of the coating film. On the other hand, when it is rolled up, the coating film is viewed from the width direction perpendicular to the thickness direction, so the optical path length is 10 cm, which corresponds to the width of the coating film. Therefore, for example, if the thickness of the coating film is reduced from 30 μm to 10 μm, the optical path length when viewed from directly above becomes 1 / 3, or 10 μm, and the yellowing is suppressed, but the optical path length when viewed as a roll remains unchanged at 10 cm. Therefore, the technology to suppress yellowing in a rolled state can be a different approach from conventional methods. In general, there is a trade-off between gas (water vapor) barrier properties and yellowing resistance, and the better the gas (water vapor) barrier properties, the more likely it is to yellow. A coating film of a vinylidene chloride copolymer with high water vapor barrier properties designed to have a water vapor permeability within the above range exhibits excellent content protection performance with a small thickness, so the thickness of the coating film, that is, the optical path length in the thickness direction of the coating film, is short. However, as already mentioned, the optical path length when viewed as a roll is independent of the thickness, so the color of the roll appears quite yellow compared to a roll of a vinylidene chloride copolymer coating film with low water vapor barrier properties. This is a factor that prevents the spread of aqueous dispersions of vinylidene chloride copolymers with high water vapor barrier properties.
[0017] The aqueous dispersion of this embodiment has a coating film of 50 g / m 2 By making the haze per unit area exceed 2.2%, it is possible to solve the above-mentioned problems specific to vinylidene chloride copolymers having high water vapor barrier properties. The aqueous dispersion of this embodiment has a coating film of 50 g / m 2 The haze per unit area is preferably 3.0% or more, more preferably 3.5% or more, and even more preferably 4.0% or more. By designing the haze to be within this range, the yellowing of the film coated with the aqueous dispersion in a rolled state can be suppressed.
[0018] Here, the coating film is 50 g / m 2 The mechanism by which a vinylidene chloride copolymer coating film (vinylidene chloride copolymer layer) having a haze per unit area of at least a certain level can suppress yellowing in a rolled state will be described. Haze is obtained by dividing the diffuse light transmittance by the total light transmittance. The higher the haze, the more cloudy (lower the transparency) the vinylidene chloride copolymer coating film (layer) is. In the above-mentioned example, as described above, the optical path length when viewed as a roll is unrelated to the thickness of the coating film, and when the haze is increased, the light is scattered on the way, and the effective optical path length becomes shorter than 10 cm, which corresponds to the width of the coating film. Therefore, the yellowing can be suppressed by increasing the haze. However, excessively high haze impairs visibility of the contents. 2 The haze per unit area is preferably less than 30%, more preferably less than 20%, even more preferably less than 10%, and particularly preferably less than 5.0%. In the above example, the optical path length when the coating film is viewed from directly above, i.e., the thickness of the coating film, depends on the amount of the aqueous dispersion applied, but in general applications, the thickness is about 1 to 200 μm, which is much shorter than the optical path length in the roll state, i.e., the width of the coating film. Therefore, if the upper limit of the haze is designed to be within the above range, there is no problem in terms of visibility of the contents. It is known that the coating film of the aqueous dispersion of vinylidene chloride copolymer turns white when boiled or retorted. 2 The haze per unit refers to the value before the film is subjected to any special processing.
[0019] <50g / m 2 How to measure haze per Above <50g / m 2 The standard coated film prepared by the method for preparing a standard coated film of Item 1 is measured using a haze meter (for example, "NDH7000II" manufactured by Nippon Denshoku Co., Ltd.).
[0020] As a result of the inventors' investigation, it was found that when the haze of two aqueous dispersion coating films with different film thicknesses is Hz1 and Hz2, and the haze of each film substrate alone is Hz01 and Hz02, the haze ratio (Hz2-Hz02) / (Hz1-Hz01) after subtracting the haze of each film substrate can be fitted to a linear or quadratic equation relative to Hz1. Therefore, a standard sample of 50 g / m 2 By making several samples of the standard coated film and the film thickness to be converted and fitting the results obtained from them, the above <50g / m 2 The film produced by other than the standard coating film production method is also 50g / m 2 It is possible to estimate the haze around the For example, for a PET film substrate with a haze of 2.0%, 2 The haze of the water dispersion-coated film was measured at Hz1 and 50 g / m 2 If the haze of the water dispersion-coated film is Hz2, "(Hz2-2.0) / (Hz1-2.0)=5.4526(Hz1-2.0)+0.8917" It was.
[0021] Coating film 50g / m 2 A method for designing an aqueous dispersion so that the haze around the aqueous dispersion falls within the above range will be described. Examples of methods for increasing the haze include, but are not limited to, the following methods (1) to (4). (1) Method for increasing the average particle size of vinylidene chloride copolymer particles (2) Blending particles with a different refractive index from the vinylidene chloride copolymer particles (3) Increase the moisture content of the coating (4) A method of generating microscopic cracks in the coating Below, we will explain each of the methods (1) to (4) in order.
[0022] (1) Increasing the average particle size of the vinylidene chloride copolymer particles. By increasing the average particle size of the vinylidene chloride copolymer particles, the haze of the coating film can be increased. When this method is adopted, the average particle size of the vinylidene chloride copolymer particles is preferably 170 nm or more, more preferably 180 nm or more. On the other hand, if the average particle size is too large, precipitation occurs. Therefore, the average particle size of the vinylidene chloride copolymer particles is preferably 230 nm or less, more preferably 210 nm or less, and even more preferably 200 nm or less. The average particle size of the vinylidene chloride copolymer particles can be changed by adjusting the amount of seed latex, the monomer composition, the amount of emulsifier, the initiator, etc. However, since the particle size is influenced by the size and shape of the polymerization machine, the shape and stirring speed of the stirrer, etc. in addition to the raw material recipe, it is usually not possible to uniquely determine the particle size from the raw material recipe. This method does not require the addition of other particles, and therefore can provide a coating film with the best water vapor barrier properties among the above methods. However, it has the disadvantage that settling and aggregation are likely to occur due to the large average particle size of the vinylidene chloride copolymer particles. The average particle size of the particles in the aqueous dispersion can be measured by the following method. <Method for measuring the average particle size of particles in an aqueous dispersion> The aqueous dispersion diluted 100 times is measured using a particle size distribution measuring device (e.g., "FPAR-1000" manufactured by Otsuka Electronics Co., Ltd.), and the average particle size obtained by cumulant analysis is regarded as the average particle size of the particles contained in the aqueous dispersion.
[0023] (2) Blending particles with a different refractive index from the vinylidene chloride copolymer particles By blending particles having a refractive index different from that of the vinylidene chloride copolymer particles (hereinafter simply referred to as "particles having a different refractive index") into the aqueous dispersion, the haze of the coating film can be increased. Particles with different refractive indexes need to be added in the form of a water dispersion. Methods for obtaining water dispersions of particles with different refractive indexes include, for example, a method of emulsion-polymerizing vinylidene chloride copolymer particles with a smaller amount of structural units derived from vinylidene chloride, a method of emulsion-polymerizing a polymer compound (polymer compound other than vinylidene chloride copolymer) that does not contain any structural units derived from vinylidene chloride, and a method of dispersing a hydrophobic compound in water in the presence of an additive such as an emulsifier as necessary. Particles with different refractive indexes may be of one type alone or a combination of multiple types. The average particle size of the particles with different refractive indexes can be measured by the above-mentioned <Method for measuring the average particle size of particles in a water dispersion>. The average particle size of the particles with different refractive indexes is preferably 130 nm or more, more preferably 150 nm or more, and even more preferably 170 nm or more. By designing the average particle size of the particles with different refractive indexes to be large, the haze of the coating film tends to increase, while if the average particle size is too large, precipitation will occur. Therefore, the average particle size of the particles with different refractive indexes is preferably 230 nm or less, more preferably 210 nm or less, and even more preferably 200 nm or less. The amount of particles with different refractive indexes added necessary to obtain the desired haze depends on the refractive index and particle size, but is preferably 1 part by mass or more, more preferably 1.5 parts by mass or more, when the total mass of the vinylidene chloride copolymer is 100 parts by mass in dry mass. In addition, since adding a large amount tends to impair the water vapor barrier property, the amount of particles with different refractive indexes added is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 2.0 parts by mass or less. However, even if the amount of particles with different refractive indexes added is within the above range, the haze does not necessarily increase, and attention is required in that it may occur that the particles are compatible with each other after coating and the haze does not change. This method can control the haze by adding to an existing latex with low haze, so there is no need to polymerize multiple formulations separately, which is excellent in terms of inventory management.
[0024] (3) Methods for increasing the moisture content of the coating The haze can also be increased by adjusting the type and amount of an emulsifier added to the aqueous dispersion, such as sodium alkylsulfonate. However, if the moisture content is too high, it may cause problems such as foaming during thermoforming of the coating film, so this method is preferably combined with the above method (1) or (2) as an auxiliary method.
[0025] (4) A method of generating microscopic cracks in the coating The haze can be increased by generating microscopic cracks in the coating film, for example, by adding particles with a high elastic modulus in an amount of about 10 to 20% by mass, assuming the dry mass of the aqueous dispersion to be 100% by mass. However, since microscopic cracks impair the water vapor barrier property, this method is preferably combined with the above method (1) or (2) as an auxiliary method.
[0026] <Method of measuring yellowness in roll state> The yellowness of the coating film in a rolled state can be measured by the following method. (Preparation of a sample for evaluation of yellowness in a roll state) Above <50g / m 2 The standard coated film prepared according to the standard coated film preparation method in is cut into six strips 1.5 cm wide and 20 cm long. Two strips are paired together with the coated sides overlapping. This results in strips with a substrate (PET) / PVDC / PVDC / substrate (PET) configuration. The resulting strips are wound around a shaft with a diameter of 5 mm to produce a roll. The portion of the shaft sticking out from the roll is cut off to use as an evaluation sample. (Yellowness measurement in roll state) A black sponge with a thickness of 2 cm is cut into a size of 5.5 cm x 5.5 cm x 2 cm. The transmittance of this sponge is measured using a Konica Minolta CM-5 color difference meter, and it is confirmed that the L value, a* value, and b* value are each within ±0.02. If the values are not within ±0.02, a different type of black sponge with values within ±0.02 is used. Next, a hole with a diameter of about 5 mm is made in the center of the sponge in the thickness direction, and the evaluation sample is passed through the hole. It is confirmed that the sponge is tightly attached around the evaluation sample, and the transmittance is measured using the color difference meter. Since some measurement variation occurs depending on the position of the sponge, move the sponge slightly and measure five times to calculate the average b* value. The higher the b* value, the stronger the yellowness. Measurement conditions: Color system: L*a*b* Index: YI ASTM E313-96 Field of view: 10° Main light source: D65 Secondary light source: None
[0027] The aqueous dispersion of this embodiment preferably has an absorption coefficient ε1 of 0.01 L / (g·cm) or more at a wavelength of 360 nm, which is generally referred to as ultraviolet light. The absorption coefficient ε1 is more preferably 0.03 L / (g·cm) or more, even more preferably 0.08 L / (g·cm) or more, even more preferably 0.14 L / (g·cm) or more, and particularly preferably 0.29 L / (g·cm) or more. The greater the absorption coefficient ε1 of the aqueous dispersion, the more the deterioration of the contents, the substrate, and the vinylidene chloride copolymer itself caused by ultraviolet light can be suppressed when a film coated with the aqueous dispersion is used as a packaging material. The absorption coefficient ε1 of the aqueous dispersion is preferably 1.00 L / (g·cm) or less, more preferably 0.76 L / (g·cm) or less, and even more preferably 0.61 L / (g·cm) or less. Examples of methods for controlling the extinction coefficient ε1 include methods for increasing the absorbance at a wavelength of 360 nm by adding an ultraviolet absorber to the aqueous dispersion or synthesizing vinylidene chloride copolymer using an ultraviolet absorbing monomer, as described below.
[0028] The absorbance at a wavelength of 360 nm can be measured using UV-Vis spectroscopy. In this specification, measurement using ultraviolet-visible spectroscopy means measurement under the following conditions. <If the sample is a film> The absorbance of the film is measured using a color difference meter CM-5 manufactured by Konica Minolta, Inc. The measurement conditions are as follows. Field of view: 10° Main light source: D65 Secondary light source: None <If the sample is liquid> The absorbance is measured using a UV-Visible spectrophotometer UV1280 manufactured by Shimadzu Corporation. Reference: Sample solvent (THF if the sample was dissolved in THF) Cell: Quartz cell (optical path length 1 cm)
[0029] The method for calculating the absorption coefficient ε1 at a wavelength of 360 nm will be described. A water dispersion of vinylidene chloride copolymer was applied to aluminum foil at a coating weight of 10 g / m2 after drying. 2 The solution is applied so that the concentration becomes 0.2% by mass, and then dried in a hot air dryer at 100°C for 1 minute to obtain a dried product. If the solution is liquid or there is still moisture remaining, dry it in an oven for a few more minutes until it is no longer liquid. The dried product is added to tetrahydrofuran so that the concentration becomes 0.2% by mass, and dissolved by stirring at room temperature. If any residue remains, heat and stir the solution to the extent that the tetrahydrofuran does not boil, and if it still does not dissolve, filter the liquid to remove the insoluble matter. The longer the heating time, the more likely the vinylidene chloride copolymer is to discolor due to heat, so the shorter the heating time and the lower the temperature, the better. The solution obtained is measured using the above-mentioned ultraviolet-visible spectroscopy <when the sample is liquid> to obtain the absorbance A1 at a wavelength of 360 nm. If the concentration of the dry matter dissolved in tetrahydrofuran is x [g / L], the extinction coefficient ε1 [L / (g cm)] can be calculated using the Beer-Lambert equation below. Beer-Lambert equation: A1=ε1×x×l (l: optical path length [cm]) Normally, the absorbance at a wavelength of 360 nm is governed by the content of the ultraviolet absorber, so even if a vinylidene chloride copolymer coating film is coated and dried under conditions different from the measurement method described above, the absorbance remains almost unchanged. Furthermore, when the absorbance A1 exceeds 0.8, the extinction coefficient ε1 cannot be accurately determined, so the concentration of the dried material to be dissolved is appropriately adjusted so that the absorbance falls within the range of 0.1 to 0.8, and then the extinction coefficient is determined.
[0030] (Vinylidene chloride copolymer) The vinylidene chloride copolymer contains structural units derived from vinylidene chloride and structural units derived from a monomer copolymerizable with vinylidene chloride (hereinafter, sometimes referred to as a "comonomer"). Examples of the copolymerizable monomer include a copolymerizable monomer having a reactivity ratio r1 to vinylidene chloride of less than 0.7 (sometimes referred to as a "copolymerizable monomer having a reactivity ratio r1 of less than 0.7"), a copolymerizable monomer having a reactivity ratio r1 to vinylidene chloride of 0.7 or more (sometimes referred to as a "copolymerizable monomer having a reactivity ratio r1 of 0.7 or more"), and the like. A copolymerizable monomer having a reactivity ratio r1 to vinylidene chloride of less than 0.7 is preferred.
[0031] Examples of monomers copolymerizable with vinylidene chloride (VDC) include maleic anhydride; itaconic acid; methyl acrylate (MA), methyl methacrylate (MMA), ethyl acrylate (EA), butyl acrylate (BA), ethyl methacrylate, n-butyl acrylate, n-butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, glycidyl methacrylate, glycidyl acrylate, acrylonitrile (AN), methacrylonitrile (M), and the like. (Meth)acrylic monomers such as 2-acrylamido-2-methylpropanesulfonic acid (AMPS) or a salt thereof (such as a sodium salt); styrene, 2-sulfoethylmethacrylic acid (2-SEM) or a salt thereof (such as a sodium salt); phosphate ester of methacrylate-terminated polypropylene glycol or a salt thereof (such as a sodium salt), vinyl chloride, etc., but are not limited thereto, and may be any monomer copolymerizable with vinylidene chloride. The monomers copolymerizable with vinylidene chloride may be used alone or in combination of two or more kinds.
[0032] The mass proportion of the structural units derived from vinylidene chloride, when the total mass of the vinylidene chloride copolymer is taken as 100 mass%, is preferably more than 70 mass%, more preferably 80 mass% or more, even more preferably 85 mass% or more, and even more preferably 87 mass% or more. The mass proportion is preferably 99 mass% or less, more preferably 95 mass% or less, even more preferably 93 mass% or less, and even more preferably 92 mass% or less. When the mass proportion of the structural units derived from vinylidene chloride is set within the above range, a film having a vinylidene chloride copolymer layer formed from the aqueous dispersion of the vinylidene chloride copolymer of this embodiment tends to exhibit water vapor barrier properties that adequately preserve the quality of the encapsulated contents. In particular, in a film coated with an aqueous dispersion of a vinylidene chloride copolymer in which the lower limit of the mass ratio of structural units derived from vinylidene chloride is designed to be 80 mass% or more, double bonds are generated by a dehydrohalogenation reaction of the vinylidene chloride copolymer under ultraviolet light. A polyene structure in which double bonds are linked has the characteristic of absorbing ultraviolet light. In other words, when the film and the contents packaged by the film are exposed to excessive ultraviolet light, the vinylidene chloride copolymer itself changes to a structure that absorbs ultraviolet light. As a result, the film coated with the aqueous dispersion of the vinylidene chloride copolymer of this embodiment can protect the contents from ultraviolet light more reliably than conventional ultraviolet absorbing films. On the other hand, the higher the proportion of structural units derived from vinylidene chloride, the more the dehydrochlorination reaction is promoted, and the film tends to absorb not only ultraviolet light but also visible light. Designing the upper limit of the content of structural units derived from vinylidene chloride to 99% by mass or less tends to prevent excessive discoloration of the film and reduced visibility of the contents.
[0033] The mass ratio of the structural units derived from monomers copolymerizable with vinylidene chloride, when the total mass of the vinylidene chloride copolymer is taken as 100 mass%, is preferably 30 mass% or less, more preferably 20 mass% or less, even more preferably 15 mass% or less, and even more preferably 13 mass% or less. The mass ratio is preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 7 mass% or more, and even more preferably 8 mass% or more. When the mass proportion of the structural units derived from monomers copolymerizable with vinylidene chloride is within the above range, the aqueous dispersion of the vinylidene chloride copolymer tends to have a good balance between the water vapor barrier properties and film-forming properties of the coating film.
[0034] As mentioned above, the vinylidene chloride interpolymer may optionally contain structural units derived from a comonomer having a reactivity ratio r1 with respect to vinylidene chloride of less than 0.7. The mass proportion of the structural units derived from copolymerization monomers having a reactivity ratio r1 of less than 0.7 is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 13% by mass or less, when the total mass of the vinylidene chloride copolymer (the total mass of structural units derived from vinylidene chloride, structural units derived from copolymerization monomers having a reactivity ratio r1 of less than 0.7, and structural units derived from copolymerization monomers having a reactivity ratio r1 of 0.7 or more) is taken as 100% by mass. Moreover, the above mass proportion is preferably 1% by mass or more, more preferably 5% by mass or more, and particularly preferably 7% by mass or more.
[0035] In addition, the proportion of the total mass of the structural units derived from vinylidene chloride and the structural units derived from a copolymerization monomer having a reactivity ratio r1 of less than 0.7 in the total mass of the vinylidene chloride copolymer (100% by mass) is preferably 85% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 100% by mass.
[0036] As described above, the vinylidene chloride copolymer may also optionally contain structural units derived from a copolymerization monomer having a reactivity ratio r1 to vinylidene chloride of 0.7 or more. The mass proportion of structural units derived from copolymerization monomers having a reactivity ratio r1 of 0.7 or more to vinylidene chloride is preferably 0 to 5 mass%, and more preferably 0 to 3 mass%, when the total mass of the vinylidene chloride copolymer (the total mass of structural units derived from vinylidene chloride, structural units derived from copolymerization monomers having a reactivity ratio r1 of less than 0.7, and structural units derived from copolymerization monomers having a reactivity ratio r1 of 0.7 or more) is taken as 100 mass%.
[0037] When the mass proportion of each of the structural units of the vinylidene chloride copolymer is within the above range, a film having a vinylidene chloride copolymer layer formed from the aqueous dispersion of the vinylidene chloride copolymer of this embodiment tends to exhibit water vapor barrier properties that adequately preserve the quality of the encapsulated contents.
[0038] The reactivity ratio r1 to vinylidene chloride is a general monomer reactivity ratio r1 calculated as r1=k11 / k12, where vinylidene chloride is monomer 1 (M1) and the copolymerization monomer is monomer 2 (M2), the rate constant of the reaction of the radical of M1 reacting with M1 is k11, and the rate constant of the reaction of the radical of M1 reacting with M2 is k12. In this specification, the reactivity ratio r1 is the value described in the Polymer Handbook Fourth Edition (ISBN: 0-471-48171-8). However, if multiple values are described in the Handbook, the lowest value is used. In addition, for monomers not described in the Handbook, the reactivity ratio r1 may be considered to be 0.7 or more. However, if the proportion of monomers with unknown reactivity ratios among the monomers constituting the synthesized polymer is relatively small and the magnitude relationship with the threshold value to be compared does not change regardless of the value of the reactivity ratio of the monomer with unknown reactivity ratio, it may be treated as unknown. For example, if the mass composition of VDC / MA / "monomer with unknown reactivity ratio" is 90 / 8 / 2 and it is desired to determine whether the proportion of monomers with a reactivity ratio r1 of less than 0.7 is 4 mass% or less, even if the reactivity ratio r1 of the monomer with unknown reactivity ratio is less than 0.7, the proportion of monomers with a reactivity ratio r1 of less than 0.7 as a whole is only 2 mass%. In such a case, the reactivity ratio of the monomer with unknown reactivity ratio may be treated as unknown.
[0039] As an example, the reactivity ratio r1 of some monomers to vinylidene chloride is shown. Butyl acrylate: 0.84 Ethyl acrylate: 0.58 Methyl acrylate: 0.7 Acrylic acid: 0.29 Acrylonitrile: 0.28 Methyl methacrylate: 0.02 Methacrylic acid: 0.15 Methacrylonitrile: 0.036 Vinyl chloride: 1.8
[0040] As the copolymerization monomer having a reactivity ratio r1 to vinylidene chloride of less than 0.7, known monomers can be used, and preferred are methyl methacrylate, monomers having a nitrile group, and monomers having a carboxyl group. The copolymerizable monomer having a reactivity ratio r1 of less than 0.7 may be used alone or in combination of two or more kinds, and preferably includes a monomer having a nitrile group.
[0041] The monomer having a nitrile group is preferably acrylonitrile or methacrylonitrile, and particularly preferably methacrylonitrile. The mass ratio of the structural units derived from monomers having a nitrile group is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, when the total mass of the vinylidene chloride copolymer (the total mass of structural units derived from vinylidene chloride, structural units derived from copolymerizing monomers having a reactivity ratio r1 of less than 0.7, and structural units derived from copolymerizing monomers having a reactivity ratio r1 of 0.7 or more) is taken as 100% by mass. Moreover, the above mass ratio is preferably 15% by mass or less, more preferably 13% by mass or less, and even more preferably 10% by mass or less. When the mass ratio of the structural units derived from monomers having a nitrile group is within the above range, the coating film of the aqueous dispersion of the vinylidene chloride copolymer tends to exhibit high water vapor barrier properties.
[0042] The mass ratio of the structural units derived from methacrylonitrile is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, when the total mass of the vinylidene chloride copolymer (the total mass of the structural units derived from vinylidene chloride, the structural units derived from a copolymerization monomer having a reactivity ratio r1 of less than 0.7, and the structural units derived from a copolymerization monomer having a reactivity ratio r1 of 0.7 or more) is taken as 100% by mass. Moreover, the above mass ratio is preferably 15% by mass or less, more preferably 13% by mass or less, and even more preferably 10% by mass or less. When the mass ratio of the structural units derived from methacrylonitrile is within the above range, the coating film of the aqueous dispersion of the vinylidene chloride copolymer tends to exhibit high water vapor barrier properties.
[0043] The monomer having a carboxyl group is preferably acrylic acid, itaconic acid, maleic acid, or methacrylic acid, and more preferably acrylic acid or methacrylic acid. The mass proportion of the structural units derived from monomers having a carboxyl group is preferably 0 to 2 mass%, more preferably 0 to 1 mass%, and even more preferably 0 to 0.4 mass%, when the total mass of the vinylidene chloride copolymer (the total mass of structural units derived from vinylidene chloride, structural units derived from copolymerizing monomers having a reactivity ratio r1 of less than 0.7, and structural units derived from copolymerizing monomers having a reactivity ratio r1 of 0.7 or more) is taken as 100 mass%. When the mass proportion of the structural units derived from monomers having a carboxyl group is within the above range, the coating film of the aqueous dispersion of the vinylidene chloride copolymer tends to exhibit high water vapor barrier properties.
[0044] As the monomer having a reactivity ratio r1 of 0.7 or more to vinylidene chloride, known monomers can be used, and preferred are vinyl chloride, methyl acrylate, and butyl acrylate. The copolymerizable monomer having a reactivity ratio r1 of 0.7 or more may be used alone or in combination of two or more kinds.
[0045] By copolymerizing these monomers, a film prepared from the aqueous dispersion of the vinylidene chloride copolymer has high water vapor barrier properties.
[0046] In addition, when the vinylidene chloride copolymer contains an ultraviolet absorbing copolymerization monomer (ultraviolet absorbing monomer) described later, the mass ratio of the structural unit derived from the ultraviolet absorbing monomer is preferably adjusted appropriately so that the absorption coefficient ε1 at a wavelength of 360 nm is 0.01 [L / (g·cm)] or more. The mass ratio of the structural unit derived from the ultraviolet absorbing monomer is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 2% by mass or less, based on the total mass of the vinylidene chloride copolymer being 100% by mass. In addition, the content of the structural unit derived from the ultraviolet absorbing monomer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more, based on the total mass of the vinylidene chloride copolymer being 100% by mass. When the upper limit of the content of the structural unit derived from the ultraviolet absorbing monomer is within the above range, the risk of the highly hydrophobic ultraviolet absorber precipitating after polymerization and contaminating the polymerization machine tends to decrease, and the coating film after coating tends to exhibit high water vapor barrier properties. Furthermore, the amount of very expensive ultraviolet absorbing monomers used tends to be reduced, making it possible to design products at realistic costs. In addition, when the lower limit of the content of the structural unit derived from the ultraviolet absorbing monomer is within the above range, the coating film after coating can exhibit sufficient ultraviolet absorbing properties, and when a film coated with the aqueous dispersion is used as a packaging material, the contents tend to be sufficiently protected from ultraviolet rays. In addition, the vinylidene chloride copolymer itself tends to be less likely to discolor due to ultraviolet rays.
[0047] The monomer composition of the vinylidene chloride copolymer can be evaluated by dissolving a sample taken by the following method 1) or 2) in tetrahydrofuran-d8 and performing NMR measurement.
[0048] 1) When a water dispersion of vinylidene chloride copolymer is available, a sample for NMR measurement is obtained by the following method. Freeze-dry 10 mL of the aqueous dispersion of vinylidene chloride copolymer, and collect 0.5 g of the freeze-dried product. Completely dissolve the collected freeze-dried product in 10 mL of tetrahydrofuran with a purity of 99.9% by mass or higher. If the freeze-dried product is difficult to dissolve in tetrahydrofuran, it may be heated and stirred within a range where the tetrahydrofuran does not boil. Drop 40 mL of acetone into the obtained solution, and filter the resulting precipitate. Collect the insoluble matter remaining after filtration to use as the measurement sample.
[0049] 2) When an aqueous dispersion of vinylidene chloride copolymer is not available and only a film having a vinylidene chloride copolymer layer coated with the aqueous dispersion is available, a sample for NMR measurement is obtained by the following method. Separate the vinylidene chloride copolymer (layer) from the film having the vinylidene chloride copolymer layer, collect 0.5 g, and completely dissolve it in 10 mL of tetrahydrofuran with a purity of 99.9% by mass or more. If it does not dissolve at room temperature, heat it to 60°C or less to completely dissolve it. Drop 40 mL of acetone into the solution, and filter the resulting precipitate. Collect the insoluble matter remaining after filtration to use as the measurement sample.
[0050] <Method for separating vinylidene chloride copolymer (layer) from film> As a method for separating a vinylidene chloride copolymer (layer) from a film having a vinylidene chloride copolymer layer, the following methods (A) to (C) are used when possible. When (A) is possible, use (A); when (A) is difficult and (B) is possible, use (B); when (A) and (B) are difficult and (C) is possible, use (C). (A) Physically peel off or scrape off with tweezers or other tools. (B) The vinylidene chloride copolymer does not dissolve, but is chemically separated by using a solvent that dissolves the primer, preferably acetone. (C) The vinylidene chloride copolymer is dissolved in a solvent that dissolves nothing other than the vinylidene chloride copolymer, and the vinylidene chloride copolymer is eluted and separated by drying. When separation is performed using a solvent by method (B) or (C), the vinylidene chloride copolymer is dried in a drying oven or the like to the extent that the vinylidene chloride copolymer is not decomposed, and the measurement is performed after confirming that the mass of the solvent in the separated product is 0.5 mass% or less. The drying conditions are a temperature of 50°C or less, a drying time of 10 hours or less, and, if necessary, under reduced pressure. If any of (A) to (C) is difficult and there are other means of separation, these may be used. It is preferable to wash and dry the separated product so that the content of impurities other than the vinylidene chloride copolymer in the separated product is as small as possible. The mass ratio of the above impurities in the measurement sample is preferably 0.5 mass% or less. The drying treatment conditions are a temperature of 60°C or less and a treatment time of 10 hours or less. Here, impurities refer to components that are not included in the aqueous dispersion of vinylidene chloride copolymer before coating, such as mixed primers and solvents, and do not include additives such as emulsifiers that are added to the aqueous dispersion from the beginning. The amount of emulsifier in the separated product can be measured by the following procedure. i) The mass of the dried separated product is designated as W1. ii) The separated product is washed with a large amount of pure water that is at least 50 times the mass W1. At this time, care is taken not to let the vinylidene chloride copolymer flow out together with the washed separated product. iii) The washed separated product is dried, and its mass is designated as W2. iv) The mass of the emulsifier is calculated by W1 - W2.
[0051] The NMR measurement conditions were as follows. Equipment: JEOL RESONANCE ECS400 (1H), Bruker Biospin Avance600 (13C) Observed nuclei: 1H (399.78MHz), 13C (150.91MHz) Pulse program: Single pulse (1H), zgig30 (13C) Accumulation count: 256 times (1H), 10,000 times (13C) Lock solvent: THF-d8 Chemical shift reference: THF (1H: 180 ppm, 13C: 67.38 ppm) Using the obtained NMR spectrum, the monomers are assigned, and the composition of the vinylidene chloride copolymer is identified by integrating the peaks.
[0052] As an example, for a polymer containing structural units derived from vinylidene chloride, methacrylonitrile, methyl methacrylate, and acrylic acid, 13 In the C-NMR spectrum, the content of structural units derived from vinylidene chloride is determined by integrating from 80 to 90 ppm, the content of structural units derived from methacrylonitrile is determined by integrating from 110 to 130 ppm, the content of structural units derived from methyl methacrylate is determined by integrating from 170 to 180 ppm, and the content of structural units derived from acrylic acid is determined by integrating from 180 to 200 ppm, and the composition ratio of each monomer in the total is calculated.
[0053] In calculating the above composition ratio, the peak of the COOCH3 group (a in the formula below) is integrated to determine the amount of methyl methacrylate. Methyl acrylate is another monomer that also has a COOCH3 group and is often copolymerized with vinylidene chloride. To distinguish between the two, 1 In the H-NMR spectrum, it is judged by the presence or absence of a peak of a methyl group (b in the formula below) bonded to the carbon of the main chain to which the COOCH3 group is bonded. This methyl group is not split because the carbon of the main chain to which it is bonded is not bonded to hydrogen, and the peak position is about 2 ppm. If a monomer having a methyl group other than methyl methacrylate, such as methacrylonitrile, is included, it can be judged by the number of methyl group peaks around 2 ppm. [ka]
[0054] Similarly, acrylonitrile and methacrylonitrile can be distinguished by the presence or absence of a peak for a methyl group (b in the above formula).
[0055] If necessary, the insoluble matter is subjected to additional measurements such as two-dimensional NMR measurement and infrared spectroscopy to identify the monomers. In addition, a copolymer with a known composition may be polymerized and measured in the same manner to compare the results.
[0056] The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment preferably contains any oxidizing agent, more preferably an oxidizing agent that is publicly used as a bleaching agent, and even more preferably an oxidizing agent that is publicly used as an oxygen-based bleaching agent. These oxidizing agents may be used alone or in combination of two or more kinds.
[0057] The oxygen bleaching agent is not particularly limited, but is preferably ozone, persulfates (sodium persulfate, potassium persulfate, ammonium persulfate, etc.), percarbonates (sodium percarbonate, potassium percarbonate, ammonium percarbonate, etc.), peracetic acid, or peroxides (hydrogen peroxide, etc.), and is particularly preferably hydrogen peroxide.
[0058] Other bleaching agents include chlorine bleaching agents, and are not particularly limited, but are preferably hypochlorous acid and hypochlorites (sodium hypochlorite, calcium hypochlorite, potassium hypochlorite, etc.). When using a chlorine bleaching agent, harmful chlorine may be generated, so it is preferable to make the aqueous dispersion basic, and particularly preferable to make it basic and have a buffering ability.
[0059] Those generally used as bleaching agents are preferred because they have a strong effect of suppressing yellowing. Chlorine-based bleaching agents generate chlorine gas that is harmful to the human body under acidic conditions, so the pH of the aqueous dispersion is limited. On the other hand, oxygen-based bleaching agents are more preferred because they can be designed to any pH, especially a low pH at which the dehydrochlorination reaction that causes yellowing is likely to occur. Among oxygen-based bleaching agents, hydrogen peroxide is the most preferred because it decomposes into oxygen and water and does not generate impurities that can cause odors.
[0060] The content of the oxidizing agent is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.05% by mass or more, when the total mass of the vinylidene chloride copolymer is taken as 100% by mass. As the amount of the oxidizing agent increases, the discoloration resistance of the film improves. In addition, it is preferably 5% by mass or less, and more preferably 1% by mass or less. By setting it within this range, it is possible to prevent the oxidizing agent from migrating from the film having a layer formed from the aqueous dispersion of this embodiment to the contents.
[0061] By adding the oxidizing agent, the oxidizing agent oxidizes the double bonds generated by the decomposition of the vinylidene chloride copolymer, which causes yellowing, and thus inhibits coloration. Surprisingly, the decomposition of the double bonds by the oxidizing agent added to the aqueous dispersion of the vinylidene chloride copolymer is very slow, and conveniently in practical use, yellowing is inhibited for a long period of time even after processing into a film. In addition, the vinylidene chloride copolymer decomposes preferentially from the part of the main chain skeleton that is easily decomposed. For example, the part that is easily decomposed is a structural unit derived from vinylidene chloride adjacent to a structural unit derived from a comonomer that enhances the water vapor barrier property. When an oxidizing agent is added, such structural units that are likely to cause coloring are oxidized preferentially, and since this is an irreversible reaction, the structural unit will not decompose thereafter. Therefore, even after the oxidizing agent is consumed, yellowing of the vinylidene chloride copolymer of this embodiment is suppressed. Moreover, the vinylidene chloride copolymer in which yellowing has been suppressed by adding the above-mentioned oxidizing agent surprisingly has water vapor barrier properties equivalent to those of the vinylidene chloride copolymer to which no oxidizing agent has been added, which is extremely advantageous for food packaging applications and pharmaceutical packaging applications in which high water vapor barrier properties are required. Another advantage of suppressing yellowing by adding an oxidizing agent is that it is sufficient to simply add an oxidizing agent to an existing aqueous dispersion of vinylidene chloride copolymer. Although there is a method of optimizing the monomer composition to suppress yellowing, in the vinylidene chloride copolymer of the present embodiment, yellowing can be improved by adding an oxidizing agent without changing the composition of the aqueous dispersion of the vinylidene chloride copolymer. This is convenient in the development of an aqueous dispersion of a vinylidene chloride copolymer, which usually requires a test of long-term storage stability.
[0062] If the aqueous dispersion of vinylidene chloride copolymer contains an oxidizing agent, potassium iodide is oxidized by the oxidizing agent to produce iodine in the above-mentioned ΔE*ab measurement. Since iodine is brown, discoloration of the aqueous dispersion is observed. If the aqueous dispersion contains enough oxidizing agent to suppress yellowing of the coating film, ΔE*ab will be 1.0 or more.
[0063] The amount of the oxidizing agent contained in the aqueous dispersion of the vinylidene chloride copolymer can be measured by the following oxidation-reduction titration. <Quantitative determination of oxidizing agent: Redox titration> All reagents used in the measurement are kept at 20°C. 100mL of aqueous dispersion is diluted by adding 65g of pure water to 35g of aqueous dispersion, and placed in a 250mL PP reagent bottle. 10mL of 10w / V% potassium iodide aqueous solution and 10mL of 1mol / L hydrochloric acid are dropped into the water, the lid is closed, and the mixture is stirred at 300rpm for 5 minutes with a 25mm x φ8mm stirrer. 0.1mol / L sodium thiosulfate solution is dropped into the resulting aqueous dispersion once every 30 seconds, and the end point is when the brown color disappears. The amount of sodium thiosulfate solution required to reach the end point is recorded. Measurements are performed several times, and the amount of sodium thiosulfate solution per drop is adjusted so that the drop is completed in 10 to 15 drops. After adjustment, measurements are performed three or more times, and the standard deviation is confirmed to be within 20% of the titration value, and the average value is taken as the result.
[0064] The amount of sodium thiosulfate solution dropped per 1% of solid content of the aqueous dispersion is proportional to the amount of oxidizing agent per 1% of solid content, and can be used as an index of the amount of oxidizing agent. The amount of sodium thiosulfate solution to be added per 1% solids is calculated by dividing the amount of sodium thiosulfate solution required for titration by the solids content. For example, if the amount of sodium thiosulfate solution added to a water dispersion with a solids content of 10% is 10 mL, the amount of sodium thiosulfate solution to be added per 1% solids content is 1 mL. The amount of sodium thiosulfate solution dropped per 1% solid content is preferably 0.001 mL or more, more preferably 0.01 mL or more, and even more preferably 0.1 mL or more. Within this range, a sufficient amount of oxidizing agent to suppress discoloration remains even after film formation.
[0065] A method for identifying the type of oxidizing agent contained in the aqueous dispersion includes a method in which the aqueous phase is separated by centrifugation and then analyzed by high performance liquid chromatography.
[0066] The oxidizing agent may be added to the aqueous dispersion at any timing, but is preferably added after the completion of polymerization of the vinylidene chloride copolymer, and particularly preferably immediately before coating. By shortening the time from addition of the oxidizing agent to coating as much as possible, it is possible to prevent the oxidizing agent from being deactivated in the aqueous solution, and to improve the effect of preventing yellowing after formation into a film. Although it is possible to add an oxidizing agent during the polymerization of vinylidene chloride copolymer, the oxidizing agent is reduced by the added reducing agent or decomposed by heating, and thus the maximum effect is not obtained. As described in Patent Documents 1 to 5, it is common to add peroxides or persulfates as initiators in polymerization. However, the oxidizing agent is prone to decomposition during polymerization, and the oxidizing agent added as an initiator is completely consumed, so that the aqueous dispersions described in Patent Documents 1 to 5 do not become colored when an aqueous potassium iodide solution is dropped as described above.
[0067] A stabilizer for the oxidizing agent may be added to the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment. Examples of stabilizers for the oxidizing agent include silicates, petrochemical chelating agents such as EDTA and DTPA, synthetic chelating agents such as condensed phosphates, phytic acid and phytates. In the aqueous dispersion of this embodiment, it is important that the oxidizing agent remains even after the film is applied. If the oxidizing agent is inactivated in the aqueous dispersion, the yellowing suppression effect is reduced, but by adding these stabilizers, the oxidizing agent is stabilized in the aqueous dispersion, and the yellowing suppression effect after the film is applied is improved. In addition, it is possible to reduce the variation in the discoloration speed after the film is applied due to the variation in the storage period, which is convenient in practical use.
[0068] In addition, the aqueous dispersion of the vinylidene chloride copolymer of this embodiment may contain a polymer compound in which the proportion of structural units derived from vinylidene chloride is 0% by mass (i.e., does not contain structural units derived from vinylidene chloride), i.e., a polymer compound other than the vinylidene chloride copolymer. Examples of polymer compounds other than vinylidene chloride copolymers include methyl methacrylate-butyl acrylate copolymer, methyl methacrylate-ethyl acrylate copolymer, methyl methacrylate-ethyl acrylate copolymer, and methyl methacrylate homopolymer. In the aqueous dispersion of the vinylidene chloride copolymer, the total mass ratio of the polymer compound other than the vinylidene chloride copolymer and the vinylidene chloride copolymer having a ratio of structural units derived from vinylidene chloride of 70% by mass or less is preferably more than 0% by mass and 15% by mass or less, more preferably 2% by mass or more and 10% by mass or less, and even more preferably 5% by mass or more and 10% by mass or less, when the dry mass of the aqueous dispersion is taken as 100% by mass. When the total mass ratio is within the above range, yellowing in a rolled state tends to be suppressed while maintaining the water vapor barrier property of the coating film.
[0069] The aqueous dispersion of the present embodiment preferably contains an ultraviolet absorbing agent in order to increase the absorbance at a wavelength of 360 nm, which is a region generally called ultraviolet light. On the other hand, the addition of an excessive ultraviolet absorbing agent is not preferable from the viewpoint of cost, in addition to impairing mechanical properties, transparency, and gas barrier properties. Conventionally, it has been difficult to compound an ultraviolet absorbent with an aqueous dispersion of a vinylidene chloride copolymer, because the aqueous dispersion is a heterogeneous substance in which a hydrophobic polymer is dispersed in water, and most ultraviolet absorbents are hydrophobic, so even if they are added, they cannot be dispersed in water and will precipitate. Therefore, it is preferable that the aqueous dispersion of this embodiment contains one or more of a hydrophilic UV absorber, contains emulsified and dispersed hydrophobic UV absorber particles, and at least a portion of the vinylidene chloride copolymer is a vinylidene chloride copolymer having UV-absorbing properties (i.e., the vinylidene chloride copolymer has structural units derived from UV-absorbing monomers), thereby increasing the absorbance at a wavelength of 360 nm and controlling the extinction coefficient ε1 at a wavelength of 360 nm to 0.01 L / (g cm) or more.
[0070] UV absorbents are roughly divided into two types: hydrophilic UV absorbents and hydrophobic UV absorbents. The hydrophobic ultraviolet absorbents can be further classified into polymerizable ultraviolet absorbents having radical polymerizability and non-polymerizable ultraviolet absorbents having no radical polymerizability. Hydrophilic UV absorbers dissolve in water. In food packaging and pharmaceutical packaging applications, water-soluble additives have the risk of migrating into the contents, and are restricted by national laws. On the other hand, they have the advantage of being easily dispersible in aqueous dispersions, and can be used in applications where migration into the contents is not important.
[0071] When the aqueous dispersion contains a hydrophilic ultraviolet absorber, the content of the hydrophilic ultraviolet absorber may be appropriately adjusted so that the absorption coefficient ε1 of the aqueous dispersion at a wavelength of 360 nm is 0.01 [L / (g cm)] or more, but is preferably 5.0 parts by mass or less, more preferably 2.0 parts by mass or less, and even more preferably 0.9 parts by mass or less, based on 100 parts by mass of the total mass of the vinylidene chloride copolymer in terms of dry mass. The content of the hydrophilic ultraviolet absorber is preferably 0.1 parts by mass or more, and more preferably 0.5 parts by mass or more, based on 100 parts by mass of the total mass of the vinylidene chloride copolymer in terms of dry mass.
[0072] The presence or absence of a hydrophilic ultraviolet absorber can be determined based on the absorbance at a wavelength of 360 nm of the water-soluble component obtained by the following procedure. <Determining the presence of hydrophilic UV absorbers> Dissolve 1 g of the dried aqueous dispersion of vinylidene chloride copolymer in 20 mL of tetrahydrofuran. Slowly add 30 mL of pure water dropwise to 20 mL of the resulting solution over the course of 1 hour. Stir with a stirrer during the dropwise addition. Since vinylidene chloride copolymer is hydrophobic, it will precipitate during this procedure. Stop stirring and leave to stand for 24 hours, then take 5 mL of the supernatant and filter with a membrane filter. Measure the resulting filtrate using a visible / ultraviolet spectrophotometer to determine the absorbance at a wavelength of 360 nm. The absorbance obtained by the above procedure is called the absorbance of the water-soluble component.
[0073] When the absorbance of the water-soluble component at a wavelength of 360 nm is less than 0.1, the water dispersion may be determined to not contain a hydrophilic ultraviolet absorber. The absorbance of the water-soluble component is preferably 0.4 or less, more preferably 0.2 or less, and even more preferably less than 0.1. If the absorbance of the water-soluble component is designed to be within this range, the risk of migration of the hydrophilic ultraviolet absorber to the contents when a film coated with the water dispersion is used as a packaging material can be reduced. In addition, when the packaging material comes into contact with water droplets or the like, the ultraviolet absorbing agent may migrate, which may reduce the ultraviolet absorbing properties of the film. Therefore, it is preferable to design the thickness within the above range.
[0074] Hydrophobic UV absorbers are preferable because they have low solubility in water and therefore have a low risk of migrating into the contents when a film coated with the aqueous dispersion is used as a packaging material. On the other hand, they have a problem in that they have low affinity with water, which is the medium of the aqueous dispersion, and therefore require ingenuity for dispersion. Methods for dispersing a hydrophobic ultraviolet absorber in an aqueous dispersion include a method of adding the absorber after emulsification and a method of introducing the absorber into polymer particles constituting an aqueous dispersion of a vinylidene chloride copolymer.
[0075] The emulsification can be carried out by emulsifying the ultraviolet absorber with water and an emulsifier. The average particle size of the obtained emulsion is preferably 200 nm or less, more preferably 100 nm or less. When an aqueous dispersion of a vinylidene chloride copolymer containing an ultraviolet absorber designed to have an average particle size within this range is added, the resulting coating film tends to have excellent transparency. This is because if the particle size of the ultraviolet absorber is large, the ultraviolet absorber will scatter light. The method for preparing an ultraviolet absorber emulsion having a small average particle size is not particularly limited, and any known method can be used. Examples include a method of carrying out emulsion polymerization using a polymerizable ultraviolet absorber, and a method of carrying out emulsion polymerization using a non-polymerizable ultraviolet absorber dissolved in a monomer. In the method of heating a non-polymerizable ultraviolet absorber, water, and an emulsifier, and emulsifying by applying high-speed shear, it is usually difficult to obtain an emulsion with a fine particle size. In addition, the emulsifier suitable for the method of emulsifying by shear is usually not the same as the emulsifier suitable for emulsion polymerization, and it is necessary to use an emulsifier different from the emulsifier used during polymerization of vinylidene chloride copolymer, which is a manufacturing disadvantage in terms of raw material management and cost.
[0076] When the aqueous dispersion contains a non-polymerizable ultraviolet absorber, the content of the non-polymerizable ultraviolet absorber may be appropriately adjusted so that the absorption coefficient ε1 of the aqueous dispersion at a wavelength of 360 nm is 0.01 [L / (g·cm)] or more, but is preferably less than 10 parts by mass, more preferably less than 5 parts by mass, and even more preferably 1 part by mass or less, based on 100 parts by mass of the total mass of the vinylidene chloride copolymer in dry mass. The content of the non-polymerizable ultraviolet absorber is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, based on 100 parts by mass of the total mass of the vinylidene chloride copolymer in dry mass.
[0077] The hydrophobic ultraviolet absorber is preferably a polymerizable ultraviolet absorber. The polymerizable ultraviolet absorber becomes a high molecular weight polymer ultraviolet absorber by polymerization. This is preferable because it reduces the risk of migration not only to water but also to organic solvents. In addition, by incorporating the ultraviolet absorber into the polymer main chain, phase separation due to differences in polarity is unlikely to occur, and it is also excellent in terms of transparency and mechanical properties. The polymerizable ultraviolet absorber may be used as a monomer in the polymerization of the vinylidene chloride copolymer of this embodiment. In this case, the vinylidene chloride copolymer contains a structural unit derived from the polymerizable ultraviolet absorber (ultraviolet absorbing monomer) and a structural unit derived from vinylidene chloride, and the vinylidene chloride copolymer of this embodiment itself can be said to be a polymeric ultraviolet absorber. In addition to the polymerization of the vinylidene chloride copolymer, for example, it may be used in the polymerization of the seed latex described later, or in the polymerization of the polymeric ultraviolet absorber emulsion added after polymerization. Since an increase in the amount of ultraviolet absorber added tends to impair gas barrier properties, it is preferable to use it in the polymerization of the seed latex or the polymerization of the vinylidene chloride copolymer. The amount of seed latex used relative to the vinylidene chloride copolymer is usually as small as about 5 parts by mass at most when the total mass of the vinylidene chloride copolymer is 100 parts by mass, so in order to add an effective amount of ultraviolet absorber, a large amount of polymerizable ultraviolet absorber, usually 10 to 30% by mass of the total mass of the seed latex, needs to be polymerized in the polymerization of the seed latex. For example, when the total mass of the vinylidene chloride copolymer is 100 parts by mass, it is desired to introduce 1 part by mass of polymerizable ultraviolet absorber. In that case, when the amount of seed latex used is 3 parts by mass, 33% by mass of polymerizable ultraviolet absorber in the seed latex is required. The use of a large amount of polymerizable ultraviolet absorber exceeding 10% by mass leads to an increase in the residue after polymerization and an increase in the particle size of the seed latex. Therefore, the polymerizable ultraviolet absorber is particularly preferably used for polymerization of the vinylidene chloride copolymer of the present embodiment. Also, the vinylidene chloride copolymer has high chemical resistance, and by copolymerizing the polymerizable ultraviolet absorber (ultraviolet absorbing monomer), the risk of elution of the ultraviolet absorber can be further reduced compared to normal polymeric ultraviolet absorbers, which is preferable.
[0078] By utilizing a solvent gradient chromatography method using a UV detector, the ultraviolet absorber contained in the aqueous dispersion of the vinylidene chloride copolymer of this embodiment can be analyzed. The peak derived from the compound containing the ultraviolet absorber is observed as a large peak. When the peak of the observed vinylidene chloride copolymer is significantly larger than the peak of a standard sample of the vinylidene chloride copolymer in which the ultraviolet absorber is not copolymerized, it can be considered that the ultraviolet absorber (ultraviolet absorbing monomer) is copolymerized in the vinylidene chloride copolymer. Similarly, whether or not an ultraviolet absorbent is copolymerized in the seed latex can be judged by comparing with a standard seed latex sample that does not contain an ultraviolet absorbent. In addition to the above analysis, it is more effective to purify the measurement target by acetone precipitation or methanol precipitation, and if the peak disappears, it is determined that the UV absorber is not copolymerized. If the peak components can be separated, they can be subjected to NMR or other analysis for more detailed analysis.
[0079] Examples of ultraviolet absorbents include benzophenone-based, benzotriazole-based, and triazine-based ultraviolet absorbents.
[0080] Specific examples of the benzophenone-based ultraviolet absorber include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 2-hydroxy-4-n-octoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2,2'-dihydroxy-4,4'dimethoxybenzophenone, 2,2',4'-tetrahydroxybenzophenone, 4-dodecyloxy-2-hydroxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, and 2-hydroxy-4-stearyloxybenzophenone. Specific examples of the polymerizable benzophenone-based ultraviolet absorber include 2-hydroxy-4-acryloxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone, 2-hydroxy-5-acryloxybenzophenone, 2-hydroxy-5-methacryloxybenzophenone, 2-hydroxy-4-(acryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-ethoxy)benzophenone, 2-hydroxy-4-(methacryloxy-diethoxy)benzophenone, and 2-hydroxy-4-(acryloxy-triethoxy)benzophenone.
[0081] Specific examples of the benzotriazole-based ultraviolet absorber include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3,5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-5-tert-octylphenyl)benzotriazole, and 2-(2'-hydroxy-3,5'-di-tert-octylphenyl)benzotriazole. , 2-[2'-hydroxy-3,5'-bis(α,α'-dimethylbenzyl)phenyl]benzotriazole, condensation product of methyl-3-[3-tert-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]propionate and polyethylene glycol (molecular weight 300) ("TINUVIN1130" manufactured by BASF Japan Ltd.), isooctyl-3-[3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl]propionate nate ("TINUVIN 384" manufactured by BASF Japan Ltd.), 2-(3-dodecyl-5-methyl-2-hydrophenyl)benzotriazole ("TINUVIN 571" manufactured by BASF Japan Ltd.), 2-(2'-hydroxy-3'-tert-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-4'-octoxyphenyl)benzotriazo 2-[2'-hydroxy-3'-(3'',4'',5'',6''-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, 2,2-methylenediphenylbis[4-(1,1,3,3-tetramethylbutyl-6-(2H-benzotriazol-2-yl)phenol], and 2,2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenolethyl)phenol ("TINUVIN900" manufactured by BASF Japan Ltd.). Specific examples of the polymerizable benzotriazole-based ultraviolet absorber include 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole ("RUVA-93" manufactured by Otsuka Chemical Co., Ltd.), 2-(2'-hydroxy-5'-methacryloxyethyl-3-tert-butylphenyl)-2H-benzotriazole, 2-(2'-hydroxy-5'-methacryloxypropyl-3-tert-butylphenyl)-5-chloro-2H-benzotriazole, and 3-methacryloyl-2-hydroxypropyl-3-[3'-(2"-benzotriazolyl)-4-hydroxy-5-tert-butyl]phenylpropionate ("CGL-104" manufactured by BASF Japan Ltd.).
[0082] Specific examples of triazine-based ultraviolet absorbers include 2-(2,4-dihydroxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-(2,4-dihydroxyphenyl)-4,6-diphenyl-1,3,5-triazine, and Ethylhexyl Triazone, 2-(2-Hydroxy-4-methoxyphenyl)-4,6-diphenyl-1,3,5-triazine, N,N',N''-Tri(m-tolyl)-1,3,5-triazine-2,4,6-triamine, 2,4,6-Tris(2,4-dihydroxyphenyl)-1,3,5- triazine, 2,4,6-Tris(4-butoxy-2-hydroxyphenyl)-1,3,5-triazine, 2,4-Bis(2,4-dimethylphenyl)-6-(2-hydroxy-4-n-octyloxyphenyl)-1,3,5-triazine, Bemotrizinol, and the like. Specific examples of the polymerizable triazine-based ultraviolet absorber include triazine methacrylate and triazine acrylate.
[0083] As the polymerizable ultraviolet absorber, benzotriazole-based ones are preferred. Benzotriazole-based ones have excellent ultraviolet absorption per mass, and can impart excellent ultraviolet resistance with a small amount. Among them, 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole (Otsuka Chemical Co., Ltd. "RUVA-93") is particularly preferred because of its excellent stability during emulsion polymerization.
[0084] Furthermore, the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment may contain, as necessary, various commonly used additives, for example, an antifoaming agent, a rheology modifier, a thickener, a dispersant, a stabilizer such as a surfactant, a wetting agent, a plasticizer, a colorant, a silicone oil, a light stabilizer, a silane coupling agent, an inorganic filler, a color pigment, an extender pigment, and the like. The solvent of the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment may be water alone, or may contain water and other solvents (e.g., alcohols, acetone, etc.). When other solvents are contained, the amount of such solvents is preferably 10 parts by mass or less per 100 parts by mass of water.
[0085] The pH of the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment may be adjusted using a base. The lower the pH, the lower the yellowing of the coating film, which is preferable. This is because, when the aqueous dispersion contains an oxidizing agent, the higher the pH, the easier the oxidizing agent is to decompose and is more likely to be consumed before coating, and also because, the higher the pH, the easier it is for the structural unit derived from vinylidene chloride to decompose and produce a double bond. The pH of the aqueous dispersion is preferably 4.0 or less, particularly preferably 3.0 or less, and further preferably 2.5 or less. However, when a chlorine bleach is used, toxic chlorine gas is generated under acidic conditions, so the preferred pH range is 6.0 or more. As described above, the higher the pH, the easier it is for the structural units derived from vinylidene chloride to decompose and form double bonds, so the higher the pH, the easier it is for the resin to turn yellow, regardless of whether an oxidizing agent is added or not. However, a high pH not only improves the aggregation stability of the aqueous dispersion, but also has the effect of suppressing corrosion of metals used in coating machines by acids, so that depending on the application, it is preferable to adjust the pH to a high level. Any base can be used to adjust the pH, and examples of such bases include ammonia, hydroxides such as sodium hydroxide and potassium hydroxide, and phosphates such as tetrasodium pyrophosphate and trisodium phosphate. Phosphates are preferred. Phosphates are preferred because they also have the effect of suppressing the decomposition of the oxidizing agent.
[0086] The solid content of the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment is preferably 10% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 63% by mass or less. The higher the solid content, the greater the coating amount per coating, and the higher the water vapor barrier properties per coating. If the solid content is less than 10% by mass, it is difficult to coat stably due to insufficient concentration. In addition, by increasing the coating amount per coating, the number of coatings required to obtain the target film thickness is reduced. This shortens the time that the coating film is exposed to heat during drying, and it is possible to suppress discoloration due to decomposition of the vinylidene chloride copolymer in the coating film. Furthermore, since the decomposition of the oxidizing agent due to heat is also suppressed, the effect of suppressing discoloration of the coating film due to the oxidizing agent is easily effective. Furthermore, if the solid content is less than 10% by mass, the amount of water that needs to be evaporated in the drying step is large, and coating defects such as insufficient drying are likely to occur. The solid content in the aqueous dispersion of this embodiment refers to the proportion of the total mass of all solid components contained in the aqueous dispersion, and may be only the vinylidene chloride copolymer, or may contain other resin components, the above-mentioned additives, etc. Examples of the other resin components include polymer compounds other than the above-mentioned vinylidene chloride copolymer, the seed latex described below, and polymers that coat the vinylidene chloride copolymer particles. When the solid content contains a mass proportion of components other than the vinylidene chloride copolymer, the mass proportion of the components other than the vinylidene chloride copolymer is preferably 0 to 7 mass%, more preferably 1 to 6 mass%, and even more preferably 2 to 6 mass%, relative to 100 mass% of the aqueous dispersion.
[0087] The solid content of the aqueous dispersion can be measured by the following method. <Solid content measurement> 2.5 g of the aqueous dispersion is weighed into a solid content meter SMART SYSTEM5 manufactured by CEM, and measurements are taken at 20°C and 50% RH. The results of three measurements are averaged, and the solid content is calculated using the formula (dry mass / mass of aqueous dispersion) x 100.
[0088] [Method of producing aqueous dispersion of vinylidene chloride copolymer] The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment can be produced by emulsion polymerization of a mixture of raw material monomers for the vinylidene chloride copolymer. Although not particularly limited, the emulsion polymerization is usually carried out at a temperature of 30 to 70°C. The polymerization temperature is preferably within a range of 40 to 60°C. By setting the polymerization temperature at 70°C or less, decomposition of the raw materials during polymerization can be suppressed, which is preferable. By setting the polymerization temperature at 30°C or more, the polymerization rate can be increased, which improves the efficiency of polymerization, which is preferable.
[0089] When carrying out the emulsion polymerization of vinylidene chloride, an aqueous dispersion synthesized from raw material monomers having different monomer compositions synthesized in the same or another polymerization machine may be added as a seed latex as a raw material.Preferably, it is an aqueous dispersion obtained by emulsion polymerization of an acrylic monomer or a methacrylic monomer, more preferably, an aqueous dispersion of a homopolymer or copolymer of methyl methacrylate or a copolymer of glycidyl methacrylate, and even more preferably, an aqueous dispersion of a homomethyl methacrylate polymer. The addition of seed latex is expected to increase the polymerization rate as well as improve the film-forming life of the product. Furthermore, when a polymerizable UV absorber is copolymerized with vinylidene chloride, there is an advantage that the polymerization residue derived from the unreacted polymerizable UV absorber is reduced. The benzotriazole, triazine, and benzophenone moieties of the polymerizable UV absorber are very hydrophobic, and if they are introduced into a polymerization machine that does not have a sufficient reaction field, they will precipitate and become polymerization residue. On the other hand, when a seed is used, the seed acts as a reaction field, and the UV absorber is efficiently introduced into the seed particle, so that polymerization residue is less likely to occur. The amount of the seed latex added is preferably 0 to 10 parts by mass, more preferably 1 to 5 parts by mass, and further preferably 3 to 4 parts by mass, based on 100 parts by mass of the vinylidene chloride copolymer. The seed latex is preferably added before the start of polymerization of vinylidene chloride, but the seed latex may be added continuously in parallel with the continuous addition of the monomer.
[0090] After the emulsion polymerization of the aqueous dispersion of the vinylidene chloride copolymer is completed, additional polymerization may be carried out by adding raw material monomers having a different monomer composition to the aqueous dispersion in the same or another polymerization machine. This allows the polymer formed by polymerization of the newly added monomers to form a structure that coats the vinylidene chloride copolymer particles, and is expected to improve the film formation life and the mechanical properties of the film. The amount of the polymer formed by the additional polymerization is preferably 10 parts by mass or less based on 100 parts by mass of the vinylidene chloride copolymer.
[0091] Examples of surfactants that can be used in the emulsion polymerization of the aqueous dispersion of the vinylidene chloride copolymer include anionic surfactants such as alkyl sulfate salts, alkyl benzene sulfonates, alkyl sulfosuccinates, alkyl diphenyl ether disulfonates, and alkyl sulfonates.
[0092] Examples of the polymerization initiator include persulfates such as sodium persulfate and potassium persulfate, and peroxides such as hydrogen peroxide, t-butyl hydroperoxide and cumene hydroperoxide, with t-butyl hydroperoxide being preferred.
[0093] As a polymerization activator, it is preferable to add a polymerization activator that accelerates the radical decomposition of the initiator, such as sodium hydrogen sulfite or sodium D-araboascorbate. These polymerization activators are preferably added to promote the decomposition of the polymerization initiator. However, on the other hand, in order to promote the decomposition of the oxidizing agent, the amount of addition is preferably as small as possible within the range required for radical decomposition of the polymerization initiator.
[0094] These polymerization additives are not particularly limited, and may be, for example, of the type that has been conventionally and preferably used in this technical field.
[0095] The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment preferably contains a crystal nucleating agent. The crystal nucleating agent is an additive that promotes crystallization of a film formed from the aqueous dispersion, and any known crystal nucleating agent that promotes crystallization of a resin can be used. Examples of such crystal nucleating agents include metal phosphates, metal benzoates, metal pimelates, metal rosin salts, benzylidene sorbitol, quinacridone, cyanine blue, metal oxalates, metal stearates, ionomers, high melting point PET, carbon black, metal oxides, metal sulfates, kaolin, clay, high melting point polyamides, crystalline resins having a different composition from the vinylidene chloride copolymer of the present embodiment described above, silica, titanium oxide, wax, highly crystalline vinylidene chloride polymer particles different from the vinylidene chloride copolymer of the present embodiment described above, and the like. It is also possible to use one or more of these in combination. Preferred are silica, titanium oxide, wax, and highly crystalline vinylidene chloride polymer particles, and particularly preferred are wax and highly crystalline vinylidene chloride polymer particles. The content of the crystal nucleating agent is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 2 parts by mass or less, based on 100 parts by mass of the vinylidene chloride copolymer. The content of the crystal nucleating agent is preferably more than 0 part by mass, and more preferably 0.05 part by mass or more. When multiple crystal nucleating agents are added, the total amount is used.
[0096] The term "wax" is understood herein to denote any natural or synthetic wax, including, but not limited to, hazel wax, urushi wax, sugar cane wax, palm wax, candelilla wax, jojoba oil, beeswax, spermaceti wax, ivory wax, wool wax, FT wax, paraffin wax, microwax, carnauba wax, beeswax, china wax, ozokerite, polyolefin wax and montan wax, and esters thereof.
[0097] The highly crystalline vinylidene chloride polymer particles are vinylidene chloride polymer particles whose addition increases the crystallization rate of a vinylidene chloride copolymer after film formation, and have a maximum melting peak temperature of 190°C or less as measured by DSC of preferably 160°C or more, and particularly preferably 170°C or more. Here, the maximum melting peak temperature is measured according to the melting peak measurement method described below, and the maximum peak temperature at 180° C. or less is used. Furthermore, the highly crystalline vinylidene chloride polymer particles are preferably vinylidene chloride copolymer particles, and particularly preferably vinylidene chloride copolymer particles containing structural units derived from vinylidene chloride in an amount of 91% by mass or more when the vinylidene chloride copolymer is taken as 100% by mass.
[0098] <Melt peak measurement method> (i) When an aqueous dispersion of a vinylidene chloride copolymer is available, the following method is used. A water dispersion of vinylidene chloride copolymer was applied to an aluminum plate at a dry coating weight of 10 g / m 2 The film is then coated with a Mayer bar so that the film becomes uniform, and dried in an oven maintained at 100°C for 1 minute. The dried film is peeled off with tweezers within 5 minutes to obtain a film of vinylidene chloride copolymer. 5 mg of the film is then taken and used for measurement.
[0099] (ii) When an aqueous dispersion of the vinylidene chloride copolymer is not available and only a film having a vinylidene chloride copolymer layer is available, the following method is used. The vinylidene chloride copolymer (layer) is separated from the film having the vinylidene chloride copolymer layer, and 5 mg is sampled for measurement. As a method for separating the vinylidene chloride copolymer (layer) from a film having a vinylidene chloride copolymer layer, the above-mentioned <Method for separating vinylidene chloride copolymer (layer) from a film> can be used.
[0100] The sample collected by the above method is heated to 170°C at 10°C / min under a nitrogen atmosphere using a differential scanning calorimeter (e.g., "Q-2000" manufactured by TAintsruments), and cooled to -40°C at 10°C / min. Next, the sample is heated to 190°C at 10°C / min, and measurement data is obtained up to 190°C. Of the measurement data obtained up to 190°C, data above 180°C is not used because vinylidene chloride begins to decompose above 180°C, and the maximum melting peak temperature is determined using the measurement values from -40°C to 180°C during the second heating.
[0101] In this measurement, for example, an aluminum Tzero Pan and Tzero hermetic lid (manufactured by TA Instruments) are used as a sample pan, and an empty pan is used as a reference. In other words, the maximum melting peak temperature is calculated based on the value obtained by subtracting the empty pan measurement result from the sample measurement result.
[0102] The addition of these crystal nucleating agents promotes the progress of crystallization after film formation, and the coating film exhibits high water vapor barrier properties.
[0103] The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment can be used as a coating material for films used in blister packages, food packages, and the like.
[0104] [film] The film of the present embodiment is a film produced by coating an aqueous dispersion of the vinylidene chloride copolymer of the present embodiment described above, i.e., a multilayer film having a vinylidene chloride copolymer layer coated with an aqueous dispersion of the vinylidene chloride copolymer of the present embodiment described above. The vinylidene chloride copolymer layer contains at least the vinylidene chloride copolymer described above, and may be a layer consisting of only the vinylidene chloride copolymer described above.
[0105] The film of the present embodiment preferably has a vinylidene chloride copolymer layer formed by coating an aqueous dispersion of the vinylidene chloride copolymer of the present embodiment on a film substrate. The film substrate is not particularly limited, but representative examples include films made of polyvinyl chloride, polyester, polyamide, and polypropylene. Most commonly, a film made of polyvinyl chloride is used. The thickness of the film substrate may vary depending on the material used, but is usually 8 to 300 μm. When the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment contains an ultraviolet absorber as described above, it can also impart ultraviolet absorbing properties to the film, and is therefore useful in particular when it is difficult to add an ultraviolet absorber to the film substrate. In general, cases in which it is difficult to add an ultraviolet absorber to a film substrate include cases in which it is difficult to add the absorber due to the manufacturing process, such as cellophane, and cases in which migration of additives to the contents is particularly restricted, such as in pharmaceutical packaging.
[0106] The film of the present embodiment may optionally further include at least one layer of a vinylidene chloride copolymer having chemical or physical properties different from those of the vinylidene chloride copolymer of the present embodiment, for example, a film in which an aqueous dispersion of a vinylidene chloride copolymer having a different composition is applied onto the vinylidene chloride copolymer layer of the present embodiment for the purpose of preventing blocking or improving the slipping property of the film. Another example is a film in which layers of the vinylidene chloride copolymer of the present embodiment and layers of a vinylidene chloride copolymer copolymerized with a highly plastic comonomer, such as methyl acrylate or butyl acrylate, are alternately laminated. A film having this structure is expected to have high impact resistance. In the case of a film having layers of a plurality of kinds of vinylidene chloride copolymers, the thickness of the vinylidene chloride copolymer layer is the sum of the thicknesses of all the layers. In addition, when a plurality of films each having a vinylidene chloride copolymer layer are bonded together by lamination or the like, the thickness of the vinylidene chloride copolymer layer is defined as the total thickness of all the layers.
[0107] The outermost surface of the film of this embodiment is preferably composed of a layer other than the vinylidene chloride copolymer layer formed by coating the vinylidene chloride copolymer of this embodiment. With such a layer structure, when an oxidizing agent is contained in the vinylidene chloride copolymer layer of this embodiment, it is possible to prevent the oxidizing agent from eluting and coming into contact with the contents when the film is used as a packaging material.
[0108] When the film of the present embodiment has a vinylidene chloride copolymer layer (including the case where the vinylidene chloride copolymer contains a structural unit derived from an ultraviolet absorbing monomer) formed by coating an aqueous dispersion of the vinylidene chloride copolymer of the present embodiment containing an ultraviolet absorber, it is preferable that layers other than the vinylidene chloride copolymer layer do not contain an ultraviolet absorber. Such a film is excellent in recyclability because the film base material can be recovered in a state free of ultraviolet absorbers by separating the vinylidene chloride copolymer layer containing an ultraviolet absorber. In addition, when used as a packaging material, the layer not containing an ultraviolet absorber can be made to be a layer in contact with the contents, thereby preventing the ultraviolet absorber from migrating to the contents. Any method can be used to determine whether each layer contains an ultraviolet absorber, such as time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, or a spectroscopic method such as IR or Raman. In addition, any method can be used to determine whether the vinylidene chloride copolymer layer is a layer formed by applying the aqueous dispersion of the present embodiment or obtained by another method. Examples include time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, and spectroscopy such as IR or Raman. Although a comprehensive judgment should be made, generally, one criterion for judgment is whether the layer contains an emulsifier, and if it contains an emulsifier, it can be said that the layer is formed by applying the aqueous dispersion of the present embodiment.
[0109] Whether each layer contains a hydrophilic ultraviolet absorber or not can be judged based on the absorbance at a wavelength of 360 nm of the water-soluble component obtained by the following procedure. <Determining the presence of hydrophilic UV absorbers> Dissolve 1 g of the collected layer in 20 mL of tetrahydrofuran. Slowly add 30 mL of pure water to 20 mL of the resulting solution over the course of 1 hour. Stir with a stirrer during the addition. Note that vinylidene chloride copolymer is hydrophobic, so it will precipitate during this procedure. Stop stirring and leave to stand for 24 hours, then take 5 mL of the supernatant and filter with a membrane filter. Measure the resulting filtrate using a visible / ultraviolet spectrophotometer to determine the absorbance at a wavelength of 360 nm. The absorbance obtained by the above procedure is called the absorbance of the water-soluble component. When the absorbance of the water-soluble component at a wavelength of 360 nm is less than 0.1, the aqueous dispersion may be determined to not contain a hydrophilic ultraviolet absorber. The absorbance of the water-soluble component is preferably 0.4 or less, more preferably 0.2 or less, and even more preferably less than 0.1. If the absorbance of the water-soluble component is designed to be within this range, the risk of migration of the hydrophilic ultraviolet absorber to the contents when the film is used as a packaging material can be reduced. In addition, when the packaging material comes into contact with water droplets or the like, the ultraviolet absorbing agent may migrate, which may reduce the ultraviolet absorbing properties of the film. Therefore, it is preferable to design the thickness within the above range.
[0110] The coating mass of the vinylidene chloride copolymer layer formed by coating the aqueous dispersion of the vinylidene chloride copolymer after drying is not particularly limited, but is preferably 1 g / m 2 More preferably, it is 10 g / m 2 More preferably, it is 40 g / m 2 More preferably, 80 g / m 2 By increasing the coating mass after drying, the water vapor barrier property of the entire film can be improved. However, the greater the thickness of the vinylidene chloride copolymer layer, the smaller the discoloration degree of the vinylidene chloride copolymer layer per unit volume when viewed as a single film, but the greater the discoloration degree when viewed as a roll. Thus, the thicker the vinylidene chloride copolymer layer of the film, the greater the effect of the vinylidene chloride copolymer of the present embodiment in suppressing yellowing in the rolled state.
[0111] In addition, the film of the present embodiment may optionally include a layer of a copolymer functionally adjusted mainly with a monomer other than vinylidene chloride having high polymerization activity, in addition to the vinylidene chloride copolymer layer formed by applying an aqueous dispersion of the vinylidene chloride copolymer. Examples of such layers include a primer layer formed on a film substrate using an aqueous resin emulsion or an acrylic dispersion, and the vinylidene chloride copolymer layer may be provided thereon by applying the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment described above.
[0112] The aqueous dispersion of the vinylidene chloride copolymer of the present embodiment is preferably applied to a film substrate as exemplified above and used as a blister package. The resulting blister package exhibits excellent water vapor barrier properties.
[0113] Furthermore, the film of this embodiment can be used as it is to form a clear film as a coating agent, in addition to being applied to blister packages. Since blister package applications require high water vapor barrier properties, there is a tendency to design the vinylidene chloride copolymer layer to be thicker, which makes yellowing more noticeable. In addition, the pharmaceutical industry tends to have stricter requirements for yellowing than other industries. Therefore, the film of this embodiment is particularly effective in blister package applications used in the pharmaceutical industry.
[0114] As a method for applying the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment to the surface of the substrate, a known method such as air spray, airless, roll coater, curtain flow coating, roll coating, dip coating, spin coating, etc. Usually, after the aqueous dispersion is applied to the film substrate, the film is dried by keeping it at room temperature or under heating for a predetermined time.
[0115] The film having a vinylidene chloride copolymer layer formed by applying the aqueous dispersion of the present embodiment has a water vapor transmission rate of preferably 0.4 g / (m 2 ·day) or less, and more preferably 0.3g / (m 2 ·day) or less, and more preferably 0.2 g / (m 2 ·day) or less. If the water vapor transmission rate is within this range, when the film is used as a packaging material, the contents tend to be sufficiently protected from water vapor. The lower limit of the water vapor transmission rate of the film is not particularly limited, and is, for example, 0 g / (m 2 ·day) or more, and 2 ·day) or more, and 2 10 days) or more.
[0116] The water vapor transmission rate of a film can be measured by preparing a coated film for measuring water vapor transmission rate. The method for preparing a coated film for measuring water vapor transmission rate is as follows. <Preparation of coated film for measuring water vapor transmission rate> On a stretched polyvinyl chloride film (thickness 250 μm) that had been subjected to corona discharge treatment, BASF's Emulder 381A was applied as a primer using a Mayer rod until the coating mass after drying was 2 g / m 2 Then, the film is dried in a hot air circulating dryer at 85°C for 15 seconds. A water dispersion is applied onto the film using a Mayer rod once so that the coating mass is 10 g / m2. 2 The coating is applied so that the coating weight becomes 50 g / m2, and then dried in a hot air circulating dryer at 85°C for 15 seconds. 2The resulting coated film is stored in a 40°C oven for 24 hours, and then conditioned in a constant temperature and humidity room at 20°C and 55% humidity for 2 hours. <Method for measuring water vapor permeability of film> The water vapor permeability of the obtained coated film is measured under conditions of 38°C and 90% RH using a Mocon Corporation PERMATRAN 3 / 33 water vapor permeability measuring device (unit: g / (m 2 The water vapor transmission rate is the average value of the measurements taken between 48 hours and 60 hours after the start of the measurement, and the measurement is carried out four times, and the average value is the water vapor transmission rate of the film.
[0117] A film having a vinylidene chloride copolymer layer coated with the aqueous dispersion of this embodiment has a haze of preferably 3.0% or more, more preferably 4.0% or more, even more preferably 4.5% or more, and particularly preferably 5.0% or more. When the haze is designed to be within this range, the yellowish color of the film in a rolled state tends to be suppressed. The haze of the film is preferably 40% or less, more preferably 30% or less, even more preferably 15% or less, and even more preferably 10% or less. If the haze is designed to be within this range, the visibility of the contents can be well maintained when the film is used as a packaging material.
[0118] The haze of a film can be measured by preparing a coated film for haze measurement, which is prepared as follows. <Preparation of coated film for haze measurement> On a stretched polyvinyl chloride film (thickness 250 μm) that had been subjected to corona discharge treatment, BASF's Emulder 381A was applied as a primer using a Mayer rod until the coating mass after drying was 2 g / m 2 Then, the film is dried in a hot air circulating dryer at 85°C for 15 seconds. A water dispersion is applied onto the film using a Mayer rod once so that the coating mass is 10 g / m2. 2The coating is applied so that the coating weight becomes 50 g / m2, and then dried in a hot air circulating dryer at 85°C for 15 seconds. 2 The resulting coated film is stored in a 40°C oven for 24 hours, and then conditioned in a constant temperature and humidity room at 20°C and 55% humidity for 2 hours. <Method of measuring film haze> The haze (%) of the resulting coated film was measured using a haze meter ("NDH7000II" manufactured by Nippon Denshoku Co., Ltd.).
[0119] Hereinafter, a method for estimating the absorption coefficient ε1 of the vinylidene chloride copolymer (PVDC layer) at a wavelength of 360 nm from a film having a vinylidene chloride copolymer (PVDC) layer formed by coating an aqueous dispersion of the vinylidene chloride copolymer of this embodiment will be described.
[0120] First, the method for calculating the absorption coefficient ε4 of the film at a wavelength of 360 nm will be explained below. The film is used as a measurement sample, and the absorbance A at a wavelength of 360 nm is 360all Separately, the absorbance at a wavelength of 360 nm of each layer other than the PVDC layer is measured separately, and the absorbances A1, A2, ... A of each layer at a wavelength of 360 nm are measured. i (i is the layer number). Absorbance A of PVDC layer at 360 nm 360PVDC can be calculated using the following formula (1). A 360PVDC =A 360all -Σ(A j ) ···(1) (In the formula, j represents an integer from 1 to i.) Obtained A 360PVDC By substituting the thickness d [cm] of the PVDC layer into the Beer-Lambert equation below, the absorption coefficient of the film ε4 [cm -1 ] can be obtained. Beer-Lambert formula: A 360PVDC = ε4×d Here, the thickness d of the PVDC layer is determined by subtracting the thicknesses of the layers other than the PVDC layer from the total thickness of the film. Most accurately, the thickness of the PVDC layer is measured by observing the cross section of the film in the thickness direction using a SEM or the like.
[0121] A 360PVDC As is clear from the calculation formula (1), A 360PVDC Must be A 360all is smaller than A. 360all and the thickness d of the PVDC layer is calculated using the Beer-Lambert equation (A 360all = ε360max × d), ε4 is smaller than the absorption coefficient ε360max obtained by substituting
[0122] Next, we will explain the relationship between the absorption coefficient ε4 of the film at a wavelength of 360 nm and the absorption coefficient ε1 of the PVDC layer. ε4 is affected by the drying conditions and the substrate. However, since the absorption coefficient at a wavelength of 360 nm is dominated by the ultraviolet absorbing substance, it is possible to obtain a converted ε4 with a value close to ε1 by converting the units of ε4. The conversion formula is as follows: Conversion ε4 = ε4 / (1000 × density of PVDC layer) The density of the PVDC layer [g / cm 3 ] can be measured using a dry density meter using helium gas. The conversions ε4 and ε1 are essentially close in meaning, and if the conversion ε4 is within the range described above for ε1, then it is highly likely that ε1 is also within the range.
[0123] [Paper laminate] The paper laminate of this embodiment is a coated paper prepared by coating with the aqueous dispersion of the vinylidene chloride copolymer of this embodiment described above, i.e., a multi-layer paper having a vinylidene chloride copolymer layer coated with the aqueous dispersion of the vinylidene chloride copolymer of this embodiment described above. The vinylidene chloride copolymer layer contains at least the vinylidene chloride copolymer described above, and may be a layer consisting of only the vinylidene chloride copolymer described above. The paper laminate of this embodiment can be used as moisture-proof paper.
[0124] The paper laminate of this embodiment preferably has a vinylidene chloride copolymer layer formed by coating an aqueous dispersion of the vinylidene chloride copolymer of this embodiment on a paper base material. The paper base material of the present embodiment is preferably composed of pulp and a filler, and may contain various chemicals as necessary. The paper base material is preferably in the form of a sheet. Examples of the paper base material in this embodiment include various well-known papers such as fine paper, medium quality paper, coated paper, one-side glossy paper, kraft paper, one-side glossy kraft paper, bleached kraft paper, glassine paper, paperboard, white paperboard, and liner.
[0125] The pulp constituting the paper base material may be chemical pulp such as bleached hardwood kraft pulp (LBKP), bleached softwood kraft pulp (NBKP), unbleached hardwood pulp (LUKP), unbleached softwood pulp (NUKP), sulfite pulp, etc., mechanical pulp such as stone grind pulp and thermomechanical pulp, wood fibers such as deinked pulp and waste paper pulp, non-wood fibers obtained from kenaf, bamboo, hemp, etc., and these may be used in appropriate combinations. Among these, it is preferable to use wood fiber pulp, chemical pulp, and mechanical pulp, and it is more preferable to use chemical pulp, because foreign matter is less likely to be mixed into the base paper, discoloration is less likely to occur over time when the laminate (packaging container) after use is used as a waste paper raw material for recycling, the surface texture is good when printed due to its high whiteness, and the value of use is high, especially when used as a packaging material.
[0126] The average fiber length of the pulp fibers constituting the paper base material is preferably 5 mm or less, and the average fiber width is preferably 100 μm or less. The fiber length and fiber width of the pulp fibers affect the size of the capillaries formed in the gaps between the pulp fibers in the paper base material, and the smaller the fiber length and fiber width of the pulp fibers, the smaller the capillaries, and the more suppressed the absorption of the aqueous dispersion of the vinylidene chloride copolymer into the paper base material. Furthermore, since the mechanical strength of the paper base material is increased, the coating speed of the aqueous dispersion can be increased, and it is also easy to mold the paper base material into a packaging container, etc. The average fiber length of the pulp fibers is more preferably 4 mm or less, further preferably 3 mm or less, and particularly preferably 2 mm or less. There is no particular lower limit, but in order to obtain an appropriate mechanical strength, it is preferably 1 mm or more. The average fiber width of the pulp fibers is more preferably 50 μm or less, further preferably 40 μm or less, and particularly preferably 30 μm or less. Although there is no particular lower limit, in order to obtain an appropriate mechanical strength, it is preferably 10 μm or more. The average fiber length and average fiber width of pulp fibers are measured by the following method. Ion-exchanged water and paper base material are weighed out so that the paper base material is 0.1 mass % and the total amount is 300 g, and a high-shear homogenizer (for example, Nippon Seiki Co., Ltd., product name "Excel Auto Homogenizer ED-7") is used to perform a fiberization process (15,000 rpm x 5 minutes) to form a slurry. The obtained slurry is cast on mica, air-dried, and measured with a high-resolution scanning electron microscope (SEM). In the particle image obtained during the measurement, the major axis (L) and minor axis (D) of 100 to 150 arbitrarily selected particles are measured, and the average values of these are taken as the average fiber length and average fiber width, respectively.
[0127] As the filler constituting the paper base material, known fillers such as white carbon, talc, kaolin, clay, calcium bicarbonate, light calcium carbonate, titanium oxide, zeolite, and synthetic resin fillers can be used.
[0128] Furthermore, in order to improve adhesion between the vinylidene chloride copolymer and the paper base material and retention, the paper base material may contain various chemicals or may be surface-treated with various chemicals, such as sizing agents, water-resistant agents, and paper strength agents.
[0129] Examples of the sizing agent include styrene-based sizing agents, alkyl ketene dimers (AKD), alkenyl succinic anhydrides (ASA), neutral rosin sizing agents, rosin sizing agents, modified rosin emulsion sizing agents, etc. Among these, rosin sizing agents and modified rosin emulsion sizing agents are preferred. The rosin sizing agent may be one that has been conventionally known in the papermaking field, and is not particularly limited. Examples of rosin-based substances include reinforced rosins obtained by modifying rosins such as gum rosin, wood rosin, and tall oil rosin with α,β-unsaturated carboxylic acids such as fumaric acid, maleic acid, and acrylic acid or their anhydrides, and rosin esters obtained by reacting the above rosins with polyhydric alcohols such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and diglycerin. The rosin sizing agent also includes emulsions of these alone or a mixture of these, and emulsions of each alone and then mixed. Furthermore, the above emulsions also include those to which various polymers have been added in order to further improve sizing properties. The content of the sizing agent in the paper base material is preferably 0.1 to 10 kg / t in terms of solid content. When the content of the sizing agent is within the above range, water absorption and repelling into the paper base material can be suppressed when the aqueous dispersion of vinylidene chloride copolymer particles is applied.
[0130] Examples of the water-resistant agent include melamine formaldehyde resins having a methylol group, an aldehyde group, an epoxy group, etc., glyoxal resins, polyamide epoxy resins, and ammonium zirconium carbonate. The content of the waterproofing agent in the paper base material is preferably 0.02 to 3 parts by mass per 100 parts by mass of pulp. When the content of the waterproofing agent is within the above range, excellent initial adhesive strength can be obtained.
[0131] The paper base material may also contain a paper strength enhancer to impart strength. As the paper strength enhancer, various known ones such as polyacrylamide resin, polyamide resin, polyamine resin, acrylic resin, melamine resin, urea resin, polyamide epichlorohydrin resin, etc. can be used. Among these, it is preferable to use an amphoteric paper strength enhancer, and amphoteric polyacrylamide is particularly preferable. Amphoteric polyacrylamides include acrylamide and anionic monomers (unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, 2-(meth)acrylamido-N-glycolic acid, and N-acryloylglycine; unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, and citraconic acid; unsaturated tricarboxylic acids such as aconitic acid and 3-butene-1,2,3-tricarboxylic acid; unsaturated tetracarboxylic acids such as 1-pentene-1,1,4,4-tetracarboxylic acid, 4-pentene-1,2,3,4-tetracarboxylic acid, and 3-hexene-1,1,6,6-tetracarboxylic acid; unsaturated sulfonic acids such as vinyl sulfonic acid, styrene sulfonic acid, and 2-acrylamido-2-methylpropane sulfonic acid). unsaturated phosphonic acids such as vinylphosphonic acid and α-phenylvinylphosphonic acid; alkali metal salts such as sodium and potassium salts or ammonium salts of the above-mentioned anionic vinyl monomers) and cationic monomers (dimethylaminoethyl methacrylate, diallyldimethylammonium chloride, diallyldiethylammonium chloride, methacryloyloxyethyltrimethylammonium methyl sulfate, methacryloyloxyethyltrimethylammonium methyl chloride, methacrylamidepropyltrimethylammonium chloride, etc.), Mannich modified products and Hoffman decomposition products of copolymers of acrylamide and the above-mentioned anionic monomers. Since amphoteric polyacrylamide has a self-fixing function, even if the amount is increased to improve inter-paper strength, the amount of cations does not become excessive, and the modified rosin emulsion sizing agent can be stably fixed. The content of the paper strength enhancer in the paper base material is preferably 12 kg / t or more and 20 kg / t or less in terms of solid content. By setting the content of the paper strength enhancer in the above range, various paper strengths such as interlaminar strength can be imparted. If the content of the paper strength enhancer is below the above range, the interlaminar strength may be insufficient. On the other hand, if the content of the paper strength enhancer exceeds the above range, the improvement of the interlaminar strength will remain almost flat, and further, the retention of the added paper strength enhancer will decrease, causing stains and foaming in the papermaking machine system, which may decrease the operability. Therefore, aluminum sulfate and various anionic, nonionic, or amphoteric retention improvers, drainage improvers, and internal additives for papermaking may be used as necessary.
[0132] Furthermore, the paper base material may contain additives such as dyes, fluorescent whitening agents, pH adjusters, defoamers, pitch control agents, slime control agents, etc. as necessary. These agents may be conventionally known in the papermaking field and are not particularly limited. The content of these additives in the paper base material is preferably 500 kg / t or less in terms of solid content.
[0133] The basis weight of the paper base material is preferably 200 g / m from the viewpoint of flexibility for use in packaging applications such as packaging materials for food and medicine, containers, cups, etc. 2 Less than 100 g / m 2 Less than 80 g / m, more preferably 80 g / m 2 Below 70 g / m 2 The lower limit is not particularly set, but the preferred range is 10 g / m 2 That's all.
[0134] The paper substrate may be a single layer, or may be made up of two or more layers.
[0135] The paper laminate of this embodiment may optionally further include a layer of at least one type of vinylidene chloride copolymer having chemical or physical properties different from those of the vinylidene chloride copolymer of this embodiment. For example, there may be mentioned a paper laminate in which an aqueous dispersion of a vinylidene chloride copolymer having a different composition is applied onto a layer coated with an aqueous dispersion of the vinylidene chloride copolymer of this embodiment for the purpose of preventing blocking or improving the slipperiness of the paper laminate. Another example is a paper laminate in which layers of the vinylidene chloride copolymer of the present embodiment and layers of a vinylidene chloride copolymer copolymerized with a highly plastic comonomer, such as methyl acrylate or butyl acrylate, are alternately laminated. A paper laminate having this structure is expected to have high impact resistance. In the case of such a paper laminate having layers of multiple types of vinylidene chloride copolymers, the thickness of the vinylidene chloride copolymer layer is the sum of the thicknesses of all the layers. In addition, when a plurality of sheets of paper having a vinylidene chloride copolymer layer are laminated together, the thickness of the vinylidene chloride copolymer layer is defined as the total thickness of all the layers.
[0136] The outermost surface of the paper laminate of this embodiment is preferably composed of a layer other than the vinylidene chloride copolymer layer coated with the vinylidene chloride copolymer of this embodiment. With such a layer structure, when an oxidizing agent is contained in the vinylidene chloride copolymer layer of this embodiment, it is possible to prevent the oxidizing agent from eluting and coming into contact with the contents when the paper laminate is used as a packaging material.
[0137] The coating mass of the vinylidene chloride copolymer layer formed by coating the aqueous dispersion of the vinylidene chloride copolymer after drying is not particularly limited, but is preferably 1 g / m 2 More preferably, it is 10 g / m 2 More preferably, it is 40 g / m 2 More preferably, 80 g / m 2 By increasing the coating film mass after drying, the water vapor barrier properties of the entire paper laminate can be improved. However, the thicker the vinylidene chloride copolymer layer, the smaller the discoloration degree of the vinylidene chloride copolymer layer per unit volume when viewed as a single sheet of paper laminate, but the larger the discoloration degree appears when rolled up. Thus, the thicker the vinylidene chloride copolymer layer of the paper laminate, the greater the effect of the vinylidene chloride copolymer of this embodiment in suppressing yellowing in the rolled state.
[0138] Furthermore, the paper laminate of this embodiment may optionally include a layer of a copolymer functionally adjusted mainly with a monomer other than vinylidene chloride having high polymerization activity, in addition to the vinylidene chloride copolymer layer formed by applying an aqueous dispersion of the vinylidene chloride copolymer. Such a layer may be, for example, a primer layer formed on a paper substrate using an aqueous resin emulsion or an acrylic dispersion, on which the vinylidene chloride copolymer layer may be provided by applying the aqueous dispersion of the vinylidene chloride copolymer of this embodiment described above.
[0139] When the paper laminate of this embodiment has a vinylidene chloride copolymer layer (including the case where the vinylidene chloride copolymer contains a structural unit derived from an ultraviolet absorbing monomer) formed by coating an aqueous dispersion of the vinylidene chloride copolymer of this embodiment containing an ultraviolet absorbent, it is preferable that layers other than the vinylidene chloride copolymer layer do not contain an ultraviolet absorbent. By separating the vinylidene chloride copolymer layer containing an ultraviolet absorbent, such a paper laminate can be recovered in a state free of ultraviolet absorbents, and is excellent in recyclability. In addition, when used as a packaging material, the layer that does not contain an ultraviolet absorbent can be used as a contact layer with the contents, thereby preventing the ultraviolet absorbent from migrating to the contents. Any method can be used to determine whether each layer has an ultraviolet absorber or not, such as time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, or a spectroscopic method such as IR or Raman. In addition, any method can be used to determine whether the vinylidene chloride copolymer layer is a layer formed by applying the aqueous dispersion of the present embodiment or obtained by another method. Examples include time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, and spectroscopy such as IR or Raman. Although a comprehensive judgment should be made, generally, one criterion for judgment is whether the layer contains an emulsifier, and if it contains an emulsifier, it can be said that the layer is formed by applying the aqueous dispersion of the present embodiment.
[0140] Whether each layer contains a hydrophilic ultraviolet absorber can be determined based on the absorbance at a wavelength of 360 nm of the water-soluble component obtained by the following procedure. <Determining the presence of hydrophilic UV absorbers> Dissolve 1 g of the collected layer in 20 mL of tetrahydrofuran. Slowly add 30 mL of pure water to 20 mL of the resulting solution over the course of 1 hour. Stir with a stirrer during the addition. Note that vinylidene chloride copolymer is hydrophobic, so it will precipitate during this procedure. Stop stirring and leave to stand for 24 hours, then take 5 mL of the supernatant and filter with a membrane filter. Measure the resulting filtrate using a visible / ultraviolet spectrophotometer to determine the absorbance at a wavelength of 360 nm. The absorbance obtained by the above procedure is called the absorbance of the water-soluble component. When the absorbance of the water-soluble component at a wavelength of 360 nm is less than 0.1, the aqueous dispersion may be determined to not contain a hydrophilic ultraviolet absorber. The absorbance of the water-soluble component is preferably 0.4 or less, more preferably 0.2 or less, and even more preferably less than 0.1. If the absorbance of the water-soluble component is designed to be within this range, the risk of migration of the hydrophilic ultraviolet absorber into the contents when the paper laminate is used as a packaging material can be reduced. In addition, when the packaging material comes into contact with water droplets or the like, the UV absorbent may migrate, which may reduce the UV absorbency of the paper laminate, so it is preferable to design it within the above range.
[0141] In recent years, paper packaging has been attracting attention due to the increasing need to reduce the amount of plastic used. Paper has a drawback in that it discolors and deteriorates due to ultraviolet light, but a paper laminate having a vinylidene chloride copolymer layer formed by applying an aqueous dispersion of the vinylidene chloride copolymer of the present embodiment containing an ultraviolet absorbent, the vinylidene chloride copolymer layer has ultraviolet light absorbing properties, so that ultraviolet deterioration of the paper is suppressed. Furthermore, when used as a packaging material, ultraviolet deterioration of the contents can also be prevented. In the case of a resin-based film, it is possible to prevent deterioration to some extent by introducing an ultraviolet absorber into the film, but in the case of paper, it is difficult or disadvantageous in terms of cost to introduce an ultraviolet absorber into the paper. Therefore, in general, when imparting ultraviolet absorption properties, it is necessary to provide an ultraviolet absorbing layer separately from a water vapor barrier layer, but the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment can form a vinylidene chloride copolymer layer having both water vapor barrier properties and ultraviolet absorbing properties by simply coating it alone, and it is possible to block oxygen, water vapor, and ultraviolet rays all at once.
[0142] As a method for applying the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment described above to the surface of the substrate, known methods such as air spray, airless, roll coater, curtain flow coating, roll coating, dip coating, spin coating, etc. After application to the paper substrate, the coating is usually dried by keeping it at room temperature or under heating for a predetermined time.
[0143] [Blister packaging film] The blister packaging film of this embodiment is a multilayer film having a vinylidene chloride copolymer layer formed by applying an aqueous dispersion of a vinylidene chloride copolymer, and has a water vapor transmission rate of 0.4 g / (m2) at 38° C. and 90% Rh. 2 ·day) or less, and the haze is 3.0% or more. The vinylidene chloride copolymer constituting the vinylidene chloride copolymer layer contains 1.0 to 15% by mass of structural units derived from methacrylonitrile.
[0144] The vinylidene chloride copolymer layer of the blister packaging film of the present embodiment contains at least a vinylidene chloride copolymer, and may be a layer consisting of only a vinylidene chloride copolymer. The blister packaging film of the present embodiment preferably has a vinylidene chloride copolymer layer on a film substrate. The film substrate is not particularly limited, but representative examples include films made of polyvinyl chloride, polyester, polyamide, and polypropylene. Most commonly, a film made of polyvinyl chloride is used. The thickness of the film substrate may vary depending on the material used, but is usually 8 to 300 μm. When the vinylidene chloride copolymer layer contains an ultraviolet absorber, ultraviolet absorbing properties can also be imparted to the blister packaging film, which is particularly useful when it is difficult to add an ultraviolet absorber to the film substrate. In general, cases in which it is difficult to add an ultraviolet absorber to a film substrate include cases in which it is difficult to add the absorber due to the manufacturing process, such as cellophane, and cases in which migration of additives to the contents is particularly restricted, such as in pharmaceutical packaging. Examples of the ultraviolet absorber (including an ultraviolet absorbing monomer) contained in the vinylidene chloride copolymer layer include the same ones that can be contained in the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment described above, and the content may be the same.
[0145] The blister packaging film of the present embodiment may have layers of multiple types of vinylidene chloride copolymers, and in that case, the thickness of the vinylidene chloride copolymer layer is the sum of the thicknesses of all the layers. In addition, when a plurality of blister packaging films each having a vinylidene chloride copolymer layer are bonded together by lamination or the like, the thickness of the vinylidene chloride copolymer layer is defined as the total thickness of all layers.
[0146] The outermost surface of the blister packaging film of the present embodiment is preferably composed of a layer other than the vinylidene chloride copolymer layer. With such a layer structure, when an oxidizing agent is contained in the vinylidene chloride copolymer layer, the oxidizing agent can be prevented from dissolving into the contents and coming into contact with the contents.
[0147] When the blister packaging film of this embodiment has a vinylidene chloride copolymer layer (including the case where the vinylidene chloride copolymer contains a structural unit derived from an ultraviolet absorbing monomer) formed by coating with an aqueous dispersion of a vinylidene chloride copolymer containing an ultraviolet absorbent, it is preferable that layers other than the vinylidene chloride copolymer layer do not contain an ultraviolet absorbent. Such a film is excellent in recyclability because the film base can be recovered in a state free of ultraviolet absorbents by separating the vinylidene chloride copolymer layer containing an ultraviolet absorbent. In addition, by making the layer not containing an ultraviolet absorbent the layer that comes into contact with the contents, migration of the ultraviolet absorbent to the contents can be prevented. Any method can be used to determine whether each layer contains an ultraviolet absorber, such as time-of-flight secondary ion mass spectrometry (TOF-SIMS), a method in which each layer is separated and dissolved to measure absorbance or NMR, or a spectroscopic method such as IR or Raman.
[0148] In addition, whether or not each layer contains a hydrophilic ultraviolet absorber can be determined based on the absorbance at a wavelength of 360 nm of the water-soluble component obtained by the procedure described above in <Determination of the presence of a hydrophilic ultraviolet absorber>. When the absorbance of the water-soluble component at a wavelength of 360 nm is less than 0.1, the aqueous dispersion may be determined to not contain a hydrophilic ultraviolet absorber. The absorbance of the water-soluble component is preferably 0.4 or less, more preferably 0.2 or less, and even more preferably less than 0.1. If the absorbance of the water-soluble component is designed to be within this range, the risk of migration of the hydrophilic ultraviolet absorber into the contents can be reduced. In addition, the ultraviolet absorbing agent may migrate when the film comes into contact with water droplets, etc., and the ultraviolet absorbing properties of the film may decrease, so that it is preferable to design the thickness within the above range.
[0149] The coating mass of the vinylidene chloride copolymer layer formed by applying the aqueous dispersion of the vinylidene chloride copolymer after drying is not particularly limited, but is preferably 1 g / m 2More preferably, it is 10 g / m 2 More preferably, it is 40 g / m 2 By increasing the coating mass after drying, the water vapor barrier property of the entire film can be improved. However, as the thickness of the vinylidene chloride copolymer layer increases, the degree of discoloration of the vinylidene chloride copolymer layer per unit volume appears large when rolled up, even if the degree is small when viewed as a single piece of film. Thus, the blister packaging film of this embodiment exhibits an effect of suppressing yellowing in a rolled state as the thickness of the vinylidene chloride copolymer layer increases.
[0150] Furthermore, the blister packaging film of this embodiment may optionally include a layer of a copolymer functionally adjusted mainly with a monomer other than vinylidene chloride having high polymerization activity, in addition to the vinylidene chloride copolymer layer formed by applying an aqueous dispersion of the vinylidene chloride copolymer. Examples of such layers include a primer layer formed on a film substrate using an aqueous resin emulsion or an acrylic dispersion, and a vinylidene chloride copolymer layer may be provided thereon by applying an aqueous dispersion of the vinylidene chloride copolymer.
[0151] In the blister packaging film of this embodiment, when the total mass of the vinylidene chloride copolymer (the total mass of structural units derived from vinylidene chloride, structural units derived from copolymerization monomers having a reactivity ratio r1 of less than 0.7, and structural units derived from copolymerization monomers having a reactivity ratio r1 of 0.7 or more) is taken as 100 mass%, the mass proportion of structural units derived from methacrylonitrile is 1.0 to 15 mass%, more preferably 3.0 to 13 mass%, and even more preferably 5.0 to 10 mass%. When the mass proportion of structural units derived from methacrylonitrile is within the above range, the vinylidene chloride copolymer layer tends to exhibit high water vapor barrier property.
[0152] The blister packaging film of this embodiment has a water vapor transmission rate of 0.4 g / (m 2·day) or less, and preferably 0.3g / (m 2 ·day) or less, and more preferably 0.2g / (m 2 ·day) or less. If the water vapor transmission rate is within this range, the contents of the blister package can be sufficiently protected from water vapor. The lower limit of the water vapor transmission rate is not particularly limited, and is, for example, 0 g / (m 2 ·day) or more, and 2 ·day) or more, and 2 10 days) or more. The water vapor transmission rate of the blister packaging film at 38° C. and 90% Rh can be measured using the above-mentioned <Method for measuring water vapor transmission rate of film>.
[0153] The blister package film of this embodiment has a haze of 3.0% or more, preferably 4.0% or more, more preferably 4.5% or more, and even more preferably 5.0% or more. When the haze is in this range, the yellowness of the film in a rolled state can be suppressed. The haze is preferably 40% or less, more preferably 30% or less, even more preferably 15% or less, and even more preferably 10% or less. When the haze is designed to be in this range, the visibility of the contents of the blister package can be maintained well. The haze of the blister package film can be measured using the above-mentioned <Method for measuring film haze>.
[0154] In the blister packaging film of this embodiment, the absorption coefficient ε5 of the vinylidene chloride copolymer layer at a wavelength of 360 nm is preferably 0.03 L / (g·cm) or more, more preferably 0.08 L / (g·cm) or more, even more preferably 0.14 L / (g·cm) or more, and even more preferably 0.29 L / (g·cm) or more. The larger the absorption coefficient ε5 of the vinylidene chloride copolymer layer, the more the deterioration of the contents, the film substrate, and the vinylidene chloride copolymer itself due to ultraviolet rays can be suppressed. The absorption coefficient ε5 of the vinylidene chloride copolymer layer is preferably 1.00 L / (g·cm) or less, more preferably 0.76 L / (g·cm) or less, and even more preferably 0.61 L / (g·cm) or less. The absorbance A5 of the vinylidene chloride copolymer layer at a wavelength of 360 nm can be measured by the above-mentioned ultraviolet-visible spectroscopy. Examples of a method for controlling the extinction coefficient ε5 include a method for increasing the absorbance at a wavelength of 360 nm by adding an ultraviolet absorber to an aqueous dispersion for forming a vinylidene chloride copolymer layer, as in the case of the aqueous dispersion of vinylidene chloride copolymer of the above-mentioned embodiment, or by synthesizing a vinylidene chloride copolymer using an ultraviolet absorbing monomer.
[0155] The aqueous dispersion of vinylidene chloride copolymer forming the vinylidene chloride copolymer layer of the blister package film of the present embodiment may be, for example, the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment described above, containing 50 g / m 2 The water vapor transmission rate per unit area is 0.8g / (m2) at 38℃ and 90% Rh. 2 ·day) and less than 50g / m 2 An aqueous dispersion having a haze of 2.2% or more per unit mass and a content of structural units derived from methacrylonitrile in the vinylidene chloride copolymer of 1.0 to 15% by mass can be used.
[0156] The method for applying the aqueous dispersion of the vinylidene chloride copolymer to the surface of the substrate can be a known method such as air spray, airless, roll coater, curtain flow coating, roll coating, dip coating, spin coating, etc. After the aqueous dispersion is applied to the film substrate, the film is usually dried by keeping it at room temperature or under heating for a predetermined time.
[0157] The ultraviolet resistance, elution of the ultraviolet absorber, and ultraviolet absorbency of the aqueous dispersion of the vinylidene chloride copolymer of the present embodiment and the film, paper laminate, or film for blister packaging having a vinylidene chloride copolymer layer coated with the aqueous dispersion can be evaluated using the following parameters (1) to (3).
[0158] (1)UV resistance The ultraviolet resistance is a parameter of the resistance to discoloration when the vinylidene chloride copolymer is irradiated with ultraviolet light. If the vinylidene chloride copolymer layer is discolored by ultraviolet light, the appearance of the film, the paper laminate, or the film for blister packaging is impaired, so the higher the ultraviolet resistance, the better. Generally, vinylidene chloride copolymers tend to turn yellow when irradiated with ultraviolet light, but the vinylidene chloride copolymer of the present embodiment has high ultraviolet resistance when an ultraviolet absorber is included. (Preparation of measurement samples) A water dispersion of vinylidene chloride copolymer was applied to aluminum foil at a dry coating weight of 10 g / m 2 The coating is applied with a Mayer bar so that the coating becomes uniform, and then dried in an oven maintained at 100°C for 1 minute. The dried coating is peeled off with tweezers within 5 minutes, and a single film of the aqueous dispersion (vinylidene chloride copolymer layer) is collected. The single film collected is folded four times to prepare a measurement sample. (Method of measuring YI) The measurement method involves placing a measurement sample 30 mm from a light source (e.g., AS ONE's "LUV-16") and irradiating it with ultraviolet light from the light source for 5 hours in a room at 20°C. After irradiation, the yellowness YI is measured with a color difference meter using the transmittance measurement method described below. The smaller the difference (ΔYI=YI-YI0) between the YI of the film (or paper laminate or blister package film) after ultraviolet irradiation and the YI (YI0) of the film (or paper laminate or blister package film) before ultraviolet irradiation, the higher the ultraviolet resistance. ΔYI is preferably 7.0 or less, more preferably 6.0 or less, even more preferably 5.0 or less, still more preferably 4.0 or less, and particularly preferably 3.0 or less. (Transmission measurement method) The transmittance of the measurement sample is measured using a color difference meter CM-5 manufactured by Konica Minolta, Inc. The YI value is the average of three measurements. The measurement conditions are as follows. Color system: L*a*b* Index: YI ASTM E313-96 Field of view: 10° Main light source: D65 Secondary light source: None
[0159] (2) Dissolution The elution of the UV absorber is a parameter for evaluating the risk of migration of the UV absorber into the contents when a film coated with the aqueous dispersion, a paper laminate, or a film for blister packaging is used as a packaging material. Since migration of the UV absorber into the contents may cause health damage, it is preferable that the elution is small. The elution varies depending on the type of solvent used in the test. When the UV absorbent is a hydrophilic or water-containing substance, water is used as a solvent to evaluate the elution, and when the UV absorbent is a hydrophobic substance, toluene is preferably used as a solvent to evaluate the elution. The measurement method is to take 0.2 g of dried vinylidene chloride copolymer and immerse it in 10 mL of solvent. After leaving it for 12 hours to remove the dried material, the absorbance of the solvent used for immersion at a wavelength of 360 nm is measured using the above-mentioned UV-Visible Spectroscopy <When the sample is liquid>. The obtained absorbance is used as an index of dissolution. Higher absorbance means higher dissolution, which is not preferable. If the absorbance exceeds 2.0, dilute the sample so that the absorbance is between 0.1 and 1.0 and measure it. Then, since the above-mentioned Beer-Lambert equation suggests that absorbance is proportional to concentration, the absorbance is multiplied by the dilution factor to convert it. For example, if the absorbance obtained by 10-fold dilution is 0.5, the original absorbance can be converted to 5.0. The dried vinylidene chloride copolymer may be obtained by drying an aqueous dispersion of the vinylidene chloride copolymer, or by separating it from a film, a paper laminate, or a film for blister packaging by the above-mentioned <Method for separating vinylidene chloride copolymer (layer) from a film>.
[0160] The absorbance when water is used as a solvent is preferably less than 0.02, more preferably less than 0.015, even more preferably less than 0.01, and particularly preferably less than 0.005. If it is less than 0.005, it can be determined that almost all of the ultraviolet absorbent is not eluted. The absorbance when toluene is used as a solvent is preferably less than 10, more preferably less than 1.4, even more preferably less than 1.0, still more preferably less than 0.5, even more preferably less than 0.2, and particularly preferably less than 0.1. If the absorbance is less than 0.1, it can be determined that almost all of the ultraviolet absorbent is not eluted.
[0161] (3) UV absorption The ultraviolet absorbing properties of a film, a paper laminate, or a film for blister packaging having a vinylidene chloride copolymer layer can be evaluated by measuring the absorbance of the film, the paper laminate, or the film for blister packaging by ultraviolet-visible spectroscopy. The higher the absorbance, the better the ultraviolet absorbing properties, and the more the film can protect the contents when used as a packaging material. Dry coating amount 10 g / m 2 The absorbance per m is preferably 0.08 or more, more preferably 0.15 or more, even more preferably 0.20 or more, and particularly preferably 0.30 or more. The UV absorbency increases with increasing coating amount. 2 If the absorbance per unit area is 0.20 or more, it is suitable for the 10 to 20 g / m2 range, which is the most common for food packaging applications. 2 On the other hand, in applications where gas barrier properties are particularly required, such as pharmaceutical packaging, a coating weight of 40 g / m2 is required from the viewpoint of gas barrier properties. 2 ~200g / m 2 A high coating weight of 10 g / m2 is used. 2 An absorbance of 0.08 or more per 1000 nm can provide sufficient protection for the contents from ultraviolet light in such high barrier applications. EXAMPLES
[0162] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, when "parts" or "%" is used, it means "parts by mass" or "% by mass", respectively, unless otherwise specified.
[0163] <Polymerization Example of Water Dispersion> [Example A1] A glass-lined pressure reactor was charged with 1.0 part by dry mass of methyl methacrylate homopolymer seed latex with an average particle size of 50 nm, and 57 parts by mass of pure water was added thereto. After degassing with stirring, the internal temperature was maintained at 45° C. A raw material monomer mixture with a mass composition ratio of vinylidene chloride (VDC) / methacrylonitrile (MAN) / methyl methacrylate (MMA) = 91 / 5 / 4 was gradually and quantitatively injected therein over 20 hours. In parallel, an emulsifier of 1.0 part of sodium alkylbenzenesulfonate dissolved in 2.5 parts of pure water, an initiator of 0.014 parts of t-butyl hydroperoxide dissolved in 3.5 parts of pure water, and a reducing agent of 0.015 parts of sodium ascorbate dissolved in 3.5 parts of pure water were continuously and pressurized. During this time, the contents were stirred while controlling the temperature at 45°C. The polymerization yield was 99.9%. Since the polymerization yield was nearly 100%, the composition of the copolymer was nearly equal to the raw material charge ratio. Unreacted monomers were removed from the aqueous dispersion of vinylidene chloride copolymer (PVDC) thus obtained by steam stripping. After that, the pH was adjusted to 2.5 using a 20°C saturated aqueous solution of tetrasodium pyrophosphate, and the solid content was adjusted to 60 mass% using pure water. The particle size of the vinylidene chloride copolymer particles was adjusted by adjusting the amount of emulsifier in the polymerization, and as a result, the average particle size of the obtained vinylidene chloride copolymer particles was 190 nm.
[0164] [Comparative Example A1] A glass-lined pressure reactor was charged with 2.5 parts by dry mass of methyl methacrylate homopolymer seed latex with an average particle size of 40 nm, and 57 parts by mass of pure water was added thereto. After degassing with stirring, the internal temperature was maintained at 45° C. A raw material monomer mixture with a mass composition ratio of vinylidene chloride (VDC) / methyl acrylate (MA)=91 / 9 was gradually and quantitatively injected therein over 20 hours. In parallel, an emulsifier of 1.0 part of sodium alkylbenzenesulfonate dissolved in 2.5 parts of pure water, an initiator of 0.014 parts of t-butyl hydroperoxide dissolved in 3.5 parts of pure water, and a reducing agent of 0.015 parts of sodium ascorbate dissolved in 3.5 parts of pure water were continuously and pressurized. During this time, the contents were stirred while controlling the temperature at 45°C. The polymerization yield was 99.9%. Since the polymerization yield was nearly 100%, the composition of the copolymer was nearly equal to the raw material charge ratio. Unreacted monomers were removed from the aqueous dispersion of vinylidene chloride copolymer thus obtained by steam stripping. After that, the pH was adjusted to 2.5 using a 20°C saturated aqueous solution of tetrasodium pyrophosphate, and the solid content was adjusted to 60 mass% using pure water. The particle size of the vinylidene chloride copolymer particles was adjusted by adjusting the amount of emulsifier in the polymerization, and as a result, the average particle size of the obtained vinylidene chloride copolymer particles was 120 nm.
[0165] [Comparative example A2] A glass-lined pressure reactor was charged with 2.5 parts by dry mass of methyl methacrylate homopolymer seed latex with an average particle size of 40 nm, and 57 parts by mass of pure water was added thereto. After degassing with stirring, the internal temperature was maintained at 45° C. A raw material monomer mixture with a mass composition ratio of vinylidene chloride (VDC) / methacrylonitrile (MAN) / methyl methacrylate (MMA) = 91 / 5 / 4 was gradually and quantitatively injected therein over 20 hours. In parallel, an emulsifier of 1.0 part of sodium alkylbenzenesulfonate dissolved in 2.5 parts of pure water, an initiator of 0.014 parts of t-butyl hydroperoxide dissolved in 3.5 parts of pure water, and a reducing agent of 0.015 parts of sodium ascorbate dissolved in 3.5 parts of pure water were continuously and quantitatively injected. During this time, the contents were stirred while controlling the temperature at 45°C. The polymerization yield was 99.9%. Since the polymerization yield was nearly 100%, the composition of the copolymer was nearly equal to the raw material charge ratio. Unreacted monomers were removed from the aqueous dispersion of vinylidene chloride copolymer thus obtained by steam stripping. After that, the pH was adjusted to 2.5 using a 20°C saturated aqueous solution of tetrasodium pyrophosphate, and the solid content was adjusted to 60 mass% using pure water. The particle size of the vinylidene chloride copolymer particles was adjusted by adjusting the amount of emulsifier in the polymerization, and as a result, the average particle size of the obtained vinylidene chloride copolymer particles was 120 nm.
[0166] [Comparative example A3] A PMMA seed latex was synthesized in the same manner as in Example 1 of Patent Document 2, and polymerization was carried out using the PMMA seed latex in the same manner as in Example 2 of Patent Document 2. (Preparation of PMMA seed latex) 8.7m (agitated at 20 rpm) with cooling circuit 3 A polymerization autoclave was charged successively with 3908 L of demineralized water, 14 kg (6.7 g active material per kg of monomer) of powdered ammonium persulfate solution, and 814 L (100 g active material per kg of monomer of seed latex) of a sodium n-alkyl-(C10-C13)benzenesulfonate solution containing 25% active material. The autoclave was closed and then subjected to two vacuum operations at an absolute pressure of 140 mbar. The stirring speed was then increased to 60 rpm while the mixture was brought to 85° C. Once the temperature reached 84° C., 151 kg (2.87 g activator wax per kg monomer) of a 40 g / L ammonium persulfate solution was added at a constant rate over a period of 3 hours while 2100 kg of methyl methacrylate was added at a constant rate over the same period of 3 hours. After the end of the injection of methyl methacrylate and ammonium persulfate, the polymerization was continued until a temperature difference of less than 5° C. was obtained between the temperature of the reaction medium and the temperature of the cooling circuit, followed by 1 hour of post-polymerization. The stirring speed was then reduced to 20 rpm and the latex was degassed and then stripped under vacuum at 65° C. for 3 hours. The solids content of the so polymerized PMMA seed latex was according to the specification, i.e., 32-35%. The average diameter of the particles, determined by DLS, was according to the specification, i.e., 30-38 nm. (Polymerization of VDC in aqueous emulsion in the presence of prepared PMMA seed latex) A 65 L polymerization autoclave equipped with a cooling circuit was charged with 6.5 L of demineralized water. Then 793 mL of the PMMA seed latex (32.75% solids content) prepared above (corresponding to 11 g of dry material per kg of monomer) and 135 mL of a 3.7 g / L ascorbic acid solution were charged. The autoclave was subjected to two vacuum operations. The stirring speed of the medium was 110 rpm. The autoclave was heated to 23° C. A 150 L autoclave equipped with a cooling circuit was used as the premixer, which was successively charged with 18.3 L of demineralized water, 109 mL of a branched alkyl-(C12) diphenyl oxide disulfate sodium solution containing 486 g / L of active material, 84 mL of a n-alkyl-(C10-C13) benzenesulfonate sodium solution containing 25% active material, 3.49 L of a 30 g / L tetrasodium pyrophosphate solution, and 1.45 L of a 180 g / L 2-acrylamido-2-methylpropanesulfonic acid sodium salt. The premixer was subjected to two vacuum operations. The stirring speed of the medium was brought to 130 rpm. A mixture of 1.45 kg of methyl methacrylate and 0.785 kg of methacrylonitrile was introduced into the premixer, followed by 23.7 kg of vinylidene chloride. After 30 minutes of stirring, the stirring speed was reduced to 90 rpm. The temperature of the reaction medium in the autoclave was increased to 60° C. At T=59° C., 340 mL of a 71.3 g / L ammonium persulfate solution was added. The introduction of ammonium persulfate was considered as the start of the polymerization (To). At To+1 min, 47.2 kg of monomer emulsion were added at a constant rate from the premixer over 8 hours. At To+1 min, 962 mL of a 11.7 g / L ascorbic acid solution were added at a constant rate over 8 hours 45 minutes. At To+2 min, 823 mL of a 41.0 g / L ammonium persulfate solution were added at a constant rate over 8 hours 15 minutes. Once a temperature difference of 2° C. was obtained between the temperature of the reaction medium and the temperature of the cooling circuit, the latex was postpolymerized for 120 minutes. The stirring speed was reduced to 110 rpm, then the latex was heat degassed and then stripped under vacuum at 60°C (autoclave temperature) for 2 hours. The temperature of the cooling system was then brought to 60°C. After 2 hours at 60°C (cooling temperature), the stirring speed was increased to 110 rpm. After 6 hours of stripping, the latex was cooled to 20°C and then filtered through a 60 μm filtration pocket. The solids content of the latex was measured and, if necessary, adjusted by addition of water to 44% to 46% by weight. The average particle size of the obtained vinylidene chloride copolymer particles was 146 nm.
[0167] [Comparative example A4] Polymerization was carried out in the same manner as in Comparative Example A3, except for the following points. · The amount of PMMA seed latex (33.2% solid content) prepared was 781 mL (corresponding to 11 g dry material per kg monomer); The amount of demineralized water introduced into the premixer was 17.6 L; Branched alkyl (C12) diphenyl oxide disulfide containing 486g / L of active material The volume of sodium acid solution was 484 mL; No n-alkyl-(C10-C13)benzenesulfonic acid sodium solution containing 250g / L of active material was added. · The amount of 180g / L 2-acrylamido-2-methylpropanesulfonic acid sodium salt was 2.18L; The amount of methyl methacrylate was 1.3 L; and At To+1 min, 47.33 kg of monomer emulsion was added through the premixer at a constant rate over 8 h. The average particle size of the obtained vinylidene chloride copolymer particles was 155 nm.
[0168] [Example A2] The dry mass of the aqueous dispersion of Comparative Example A2 was adjusted to 98 parts by mass, and the aqueous dispersion A shown below was mixed therewith so that the dry mass became 2 parts by mass. <Synthesis of Water Dispersion A> In a glass-lined pressure reactor, 1.0 part by dry mass of methyl methacrylate homopolymer seed latex with an average particle size of 50 nm was charged, and 57 parts by mass of pure water was added thereto, and after degassing with stirring, the internal temperature was maintained at 45° C. A raw material monomer mixture with a mass composition ratio of vinylidene chloride (VDC) / butyl acrylate (BA)=60 / 40 was gradually and quantitatively injected therein over 20 hours. In parallel, an emulsifier of 1.0 part of sodium alkylbenzenesulfonate dissolved in 2.5 parts of pure water, an initiator of 0.014 parts of t-butyl hydroperoxide dissolved in 3.5 parts of pure water, and a reducing agent of 0.015 parts of sodium ascorbate dissolved in 3.5 parts of pure water were continuously and pressurized. During this time, the contents were stirred while controlling the temperature at 45°C. The polymerization yield was 99.9%. Since the polymerization yield was nearly 100%, the composition of the copolymer was nearly equal to the raw material charge ratio. Unreacted monomers were removed from the aqueous dispersion of vinylidene chloride copolymer thus obtained by steam stripping. After that, the pH was adjusted to 2.5 using a 20°C saturated aqueous solution of tetrasodium pyrophosphate, and the solid content was adjusted to 60 mass% using pure water. The particle size of the vinylidene chloride copolymer particles was adjusted by adjusting the amount of emulsifier in the polymerization, and as a result, the average particle size of the obtained vinylidene chloride copolymer particles was 190 nm.
[0169] [Example A3] The dry mass of the water dispersion of Comparative Example A2 was adjusted to 95 parts by mass, and water dispersion A synthesized by the method described in <Synthesis of water dispersion A> in Example A2 was mixed therewith so that the dry mass became 5 parts by mass.
[0170] [Example A4] The dry mass of the water dispersion of Comparative Example A2 was adjusted to 90 parts by mass, and water dispersion A synthesized by the method described in <Synthesis of water dispersion A> of Example A2 was mixed therewith so that the dry mass became 10 parts by mass.
[0171] [Example A5] The dry mass of the aqueous dispersion of Comparative Example A2 was adjusted to 90 parts by mass, and the aqueous dispersion B shown below was mixed therewith so that the dry mass became 10 parts by mass. <Synthesis of Water Dispersion B> In a glass-lined pressure reactor, 3.0 parts by dry mass of methyl methacrylate homopolymer seed latex with an average particle size of 40 nm was charged, and 185 parts by mass of pure water was added thereto, and after degassing with stirring, the internal temperature was maintained at 45° C. A raw material monomer mixture with a mass composition ratio of methyl methacrylate (MMA) / butyl acrylate (BA) = 95 / 5 was gradually and quantitatively injected therein over a period of 5 hours. In parallel, an emulsifier consisting of 1.0 part of sodium alkylbenzene sulfonate dissolved in 2.5 parts of pure water and an initiator consisting of 1.0 part of sodium sulfate dissolved in 3.5 parts of pure water were continuously and quantitatively injected. During this time, the contents were stirred while controlling the temperature at 55°C. The polymerization yield was 99.9%. Since the polymerization yield was almost 100%, the composition of the copolymer was almost equal to the raw material charge ratio. The solid content of the aqueous dispersion of the acrylic copolymer thus obtained was adjusted to 30% by mass using pure water. The particle size of the acrylic copolymer particles was adjusted by adjusting the amount of emulsifier in the polymerization, and as a result, the average particle size of the obtained acrylic copolymer particles was 131 nm.
[0172] [Comparative Example A5] The dry mass of the water dispersion of Comparative Example A2 was adjusted to 90 parts by mass, and water dispersion B synthesized by the method described in <Synthesis of water dispersion B> of Example A5 was mixed therewith so that the dry mass became 15 parts by mass.
[0173] [Comparative example A6] The dry mass of the water dispersion of Comparative Example A2 was adjusted to 75 parts by mass, and water dispersion B synthesized by the method described in <Synthesis of water dispersion B> of Example A5 was mixed therewith so that the dry mass became 25 parts by mass.
[0174] The resulting aqueous dispersion of vinylidene chloride copolymer was used to carry out the following measurements. The measurements were carried out within one day after the preparation of the aqueous dispersion, and the aqueous dispersion was stored at 5° C. until the measurements were carried out.
[0175] (50g / m 2 (Preparation of standard coated film) A 10 g / m2 aqueous dispersion was applied to a 12 μm thick PET film (haze 2.0 or less) at a dry weight. 2 This was then applied with a wire bar so that the coating was 50 g / m2, and dried in an oven heated to 80°C for 1 minute. This procedure was repeated 5 times to obtain a coating of 50 g / m2. 2 A standard coated film of 1000 g was obtained.
[0176] (10g / m 2 (Preparation of standard coated film) A 10 g / m2 aqueous dispersion was applied to a 12 μm thick PET film (haze 2.0 or less) at a dry weight. 2 Then, dry it for 1 minute in an oven heated to 80°C and apply a 10g / m 2 A standard coated film of 1000 g was obtained.
[0177] (Preparation of a sample for evaluating the color of the roll) A sample for evaluating the color of the roll was prepared as follows. Above (50g / m 2 The standard coated film of 50 g / m 2Six strips of standard coated film were cut into strips measuring 1.5 cm wide and 20 cm long. Two strips were paired together with their coated surfaces overlapping. This resulted in strips with a substrate (PET) / PVDC / PVDC / substrate (PET) configuration. The resulting strips were wound around a shaft with a diameter of 5 mm to produce a roll. The portion of the shaft sticking out from the roll was cut off to prepare an evaluation sample.
[0178] <Visual evaluation of roll color> The evaluation sample prepared as described above (preparation of sample for evaluating color tone of roll) was visually observed and evaluated for yellowness. (Evaluation Results) The rolls of Comparative Examples A2 to A4 and Example A1 were visually inspected from a direction perpendicular to the thickness direction (in a state where the standard coating films were layered) and the yellowness was evaluated. The order of perceived yellowness was Comparative Example A2>Comparative Example A3≒Comparative Example A4>Example A1. No significant difference was felt between Comparative Examples A3 and A4. Comparative Example A2 was perceived as strongly yellowish when observed through a fluorescent lamp. On the other hand, Example A1 was a whitish light yellow when observed through a fluorescent lamp. This is thought to be because the vinylidene chloride copolymer layer in Example A1 has a certain level of haze, which scatters light and makes it appear white. The rolls of Comparative Example A2, Examples A2, A3, and A4 were similarly observed and evaluated for yellowness, and the order of perceived yellowness was Comparative Example A2>Example A2>Example A3>Example A4. When observed through a fluorescent lamp, Examples 3 and 4 were quite whitish, and especially Example A4 had no perceived yellowness. The rolls of Comparative Examples A2, A5, A6, and Example A5 were similarly observed and evaluated for yellowness. The order of perceived yellowness was Comparative Example A2>Example A5>Comparative Example A5>Comparative Example A6. When observed through a fluorescent lamp, Comparative Example A6 was significantly whiter.
[0179] <Measurement of yellowness of roll color> Using the evaluation sample prepared as described above (Preparation of a sample for evaluating the color of a roll), the b* value was measured as follows. A black sponge with a thickness of 2 cm was cut into a size of 5.5 cm x 5.5 cm x 2 cm. The transmittance of this sponge was measured using a color difference meter CM-5 manufactured by Konica Minolta, Inc., and it was confirmed that the L value, a* value, and b* value were each within ±0.02. If the values were not within ±0.02, a different type of black sponge was used. Next, a hole with a diameter of about 5 mm was drilled through the center of the sponge in the thickness direction, and the evaluation sample was passed through the hole. It was confirmed that the sponge was tightly attached around the evaluation sample, and the transmittance was measured using the color difference meter. Since some measurement variation occurs depending on the position of the sponge, the sponge was moved slightly while taking the measurement five times and the average b* value was calculated. A higher b* value means a stronger yellowness. Measurement conditions: Color system: L*a*b* Index: YI ASTM E313-96 Field of view: 10° Main light source: D65 Secondary light source: None
[0180] <50g / m of vinylidene chloride copolymer layer 2 Measurement of water vapor transmission rate per Above (50g / m 2 (Preparation of standard coated film) 2 The standard coated film was stored in a 40°C oven for two days, and then the water vapor transmission rate was measured under conditions of 38°C and 90% Rh using a water vapor transmission rate measuring device PERMATRAN W-3 / 34G manufactured by Mocon. The water vapor transmission rate was the average value of the measurements taken between 48 and 60 hours after the start of the measurement. The measurement was performed four times, and the average value (g / (m 2 ·day) was used. In addition, since the water vapor permeability of a PET film is greater than that of a vinylidene chloride copolymer layer, there is no problem in using the water vapor permeability of a standard coated film as the water vapor permeability of the vinylidene chloride copolymer layer.
[0181] <10g / m 2 Haze measurements per > Above (10g / m 2 (Preparation of standard coated film) 2 The haze (%) of the standard coated film was measured using a haze meter ("NDH7000II" manufactured by Nippon Denshoku Co., Ltd.).
[0182] <50g / m 2 Haze measurements per > Above (50g / m 2 (Preparation of standard coated film) 2 The haze (%) of the standard coated film was measured using a haze meter ("NDH7000II" manufactured by Nippon Denshoku Co., Ltd.).
[0183] <Solid content measurement> 2.5 g of the aqueous dispersion was weighed into a solid content meter SMART SYSTEM5 manufactured by CEM, and measurements were performed under an environment of 20°C and 50% RH. The results of three measurements were averaged, and the solid content (mass%) was calculated using the formula (dry mass / mass of aqueous dispersion) x 100.
[0184] <Monomer composition> The monomer composition of the vinylidene chloride copolymers in the examples and comparative examples was evaluated by dissolving samples taken by the following method in tetrahydrofuran-d8 and carrying out NMR measurement. 10 mL of the aqueous dispersion was freeze-dried, and 0.5 g of the freeze-dried product was collected. The freeze-dried product was dissolved in 10 mL of tetrahydrofuran with a purity of 99.9% by mass or more, and 40 mL of acetone was added dropwise to the solution. The resulting precipitate was filtered, and the remaining insoluble matter was collected. The collected insoluble matter was used as the measurement sample. The NMR measurement conditions were as follows. Equipment: JEOL RESONANCE ECS400 (1H), Bruker Biospin Avance600 (13C) Observed nuclei: 1H (399.78MHz), 13C (150.91MHz) Pulse program: Single pulse (1H), zgig30 (13C) Accumulation count: 256 times (1H), 10,000 times (13C) Lock solvent: THF-d8 Chemical shift reference: THF (1H: 180 ppm, 13C: 67.38 ppm) The monomers were assigned using the NMR spectrum obtained, and the composition of the vinylidene chloride copolymer was identified by integrating the peaks. The type of monomers contained was clear from the monomers used. As an example, for a polymer containing structural units derived from vinylidene chloride, methacrylonitrile, methyl methacrylate, and acrylic acid, 13 In the C-NMR spectrum, the content of structural units derived from vinylidene chloride was determined by integrating from 80 to 90 ppm, the content of structural units derived from methacrylonitrile was determined by integrating from 110 to 130 ppm, the content of structural units derived from methyl methacrylate was determined by integrating from 170 to 180 ppm, and the content of structural units derived from acrylic acid was determined by integrating from 180 to 200 ppm, and the composition ratio of each monomer in the total was calculated. In the case of a copolymer containing structural units derived from methyl acrylate instead of methyl methacrylate, the calculation is performed by substituting methyl acrylate for methyl methacrylate in the above calculation method. In the case of a copolymer containing structural units derived from acrylonitrile instead of methacrylonitrile, the calculation is performed by substituting acrylonitrile for methacrylonitrile in the above calculation method. As a result of the above measurements, it was found that the vinylidene chloride copolymers obtained in the Examples and Comparative Examples had the same monomer composition as the charged composition.
[0185] Table 1 shows the measurement results of Examples A1 to A5 and Comparative Examples A1 to A6. [Table 1]
[0186] The results in Table 1 make clear that the aqueous dispersion of the vinylidene chloride copolymer of the present invention can form a coating film (vinylidene chloride copolymer layer) that exhibits reduced yellowing in a rolled state while maintaining high water vapor barrier properties.
[0187] Next, an experiment was conducted to prepare a film for blister packaging.
[0188] [Comparative Example B1] The aqueous dispersion of Comparative Example A2 was used. The aqueous dispersion of Comparative Example A2 was applied to a 100 μm-thick stretched polyvinyl chloride (PVC) film at 50 g / m as follows. 2 A film for coated blister packaging was prepared. On a PVC film (thickness 100 μm) that had been corona discharge-treated, BASF's Emulder 381A was applied as a primer using a Mayer rod until the coating mass after drying was 2 g / m 2 The film was then dried in a hot air circulating dryer at 85° C. for 15 seconds. The aqueous dispersion of Comparative Example A2 was applied onto the film using a Mayer rod once so that the coating mass after drying was 10 g / m 2 The coating is applied so that the coating weight becomes 50 g / m2, and then dried in a hot air circulating dryer at 85°C for 15 seconds. 2 The obtained coated film was placed in an oven at 40° C. and stored for 24 hours, and then conditioned in a constant temperature and humidity chamber at 20° C. and 55% humidity for 2 hours to obtain a film for blister packaging. The water vapor permeability of the obtained film for blister packaging was 0.3 g / (m 2 ·day) and the haze was 2.0%.
[0189] [Comparative example B2] The aqueous dispersion of Comparative Example A2 was used. In the same manner as in Comparative Example B1, the aqueous dispersion of Comparative Example A2 was applied to a PVC film having a thickness of 100 μm at a concentration of 80 g / m 2 A film for coated blister packaging was prepared. The water vapor permeability of the obtained film for blister packaging was 0.2 g / (m 2 ·day), and the haze was 2.4%.
[0190] [Comparative Example B3] The aqueous dispersion of Comparative Example A2 was used. In the same manner as in Comparative Example B1, the aqueous dispersion of Comparative Example A2 was applied to a PVC film having a thickness of 100 μm at a concentration of 40 g / m 2 A film for coated blister packaging was prepared. The water vapor transmission rate of the resulting film for blister packaging was 0.4 g / m 2 / day, haze was 2.0%.
[0191] [Example B1] The aqueous dispersion of Example A1 was used. The aqueous dispersion of Example A1 was applied to a PVC film having a thickness of 100 μm at a concentration of 50 g / m in the same manner as in Comparative Example B1. 2 A film for coated blister packaging was prepared. The water vapor transmission rate of the resulting film for blister packaging was 0.3 g / m 2 / day, the haze was 4.0%.
[0192] [Example B2] The aqueous dispersion of Example A1 was used. The aqueous dispersion of Example A1 was applied to a PVC film having a thickness of 100 μm at a concentration of 80 g / m in the same manner as in Comparative Example B1. 2 A film for coated blister packaging was prepared. The water vapor transmission rate of the obtained film for blister packaging was 0.2 g / m 2 / day, the haze was 6.0%.
[0193] [Example B3] The aqueous dispersion of Example A1 was used. The aqueous dispersion of Example A1 was applied to a PVC film having a thickness of 100 μm at a concentration of 40 g / m in the same manner as in Comparative Example B1. 2 A film for coated blister packaging was prepared. The water vapor transmission rate of the resulting film for blister packaging was 0.4 g / m 2 / day, haze was 3.0%.
[0194] <Visual evaluation of color of film rolls for blister packaging> Using the blister packaging films produced in the Examples and Comparative Examples, roll samples were produced in the same manner as described above (Production of sample for evaluating roll color), and the color was visually confirmed to evaluate the yellowness. (Evaluation Results) When comparing Examples and Comparative Examples having the same water vapor transmission rate, the rolls of Examples in which the film haze was 3.0% or more were whiter and less yellow than those of Comparative Examples in which the haze was less than 3.0%.
[0195] <Measurement of water vapor transmission rate of blister packaging film> The film for blister packaging was measured at 38°C and 90% RH using a water vapor transmission rate measuring device PERMATRAN 3 / 33 manufactured by Mocon. The average value of the measurements taken between 48 hours and 60 hours after the start of the measurement was taken as the water vapor transmission rate. The measurement was carried out four times, and the average value (g / (m 2 ·day) was used.
[0196] <Haze measurement of blister packaging film> The haze (%) of the blister packaging film was measured using a haze meter ("NDH7000II" manufactured by Nippon Denshoku Co., Ltd.). [Industrial Applicability]
[0197] The aqueous dispersion of the vinylidene chloride copolymer of the present invention gives a coating film that is excellent in water vapor barrier property and color in a rolled state, and therefore can be suitably used as a coating material for various materials such as packaging films for foods and medicines, paper, and general household goods.
Claims
1. When the coating is applied, the coating is 50 g / m 2 The water vapor transmission rate per unit area is 0.8 g / (m2) at 38°C and 90% Rh. 2 day), and the coating film is 50 g / m 2 2. A water dispersion of a vinylidene chloride copolymer, comprising: a dispersion of a vinylidene chloride copolymer having a haze of more than 2.2% per unit area;
2. 2. The aqueous dispersion of the vinylidene chloride copolymer according to claim 1, having a solids content of 50% by mass or more.
3. Contains polymer compounds other than vinylidene chloride copolymers, 3. The aqueous dispersion of a vinylidene chloride copolymer according to claim 1 or 2, wherein the total mass ratio of the polymer compound and a vinylidene chloride copolymer having a proportion of structural units derived from vinylidene chloride of more than 0 mass% and not more than 70 mass% is more than 0 mass% and not more than 15 mass%, when the dry mass of the aqueous dispersion of the vinylidene chloride copolymer is taken as 100 mass%.
4. the vinylidene chloride copolymer contains 1.0 to 20 mass % of structural units derived from a monomer having a reactivity ratio r1 with vinylidene chloride of less than 0.7; 3. The aqueous dispersion of a vinylidene chloride copolymer according to claim 1, wherein the copolymerization monomer having a reactivity ratio r1 of less than 0.7 is at least one selected from the group consisting of methyl methacrylate, acrylonitrile, methacrylonitrile, acrylic acid, itaconic acid, maleic acid, and methacrylic acid.
5. 5. The aqueous dispersion according to claim 4, wherein the vinylidene chloride copolymer contains 1.0 to 15% by mass of structural units derived from methacrylonitrile when the vinylidene chloride copolymer is taken as 100% by mass.
6. 3. A film or paper laminate comprising a vinylidene chloride copolymer layer formed by coating the aqueous dispersion of the vinylidene chloride copolymer according to claim 1 or 2.
7. A blister packaging film having a vinylidene chloride copolymer layer formed by applying an aqueous dispersion of a vinylidene chloride copolymer, Water vapor transmission rate is 0.4 g / (m at 38°C and 90% Rh. 2 ・day) or less, The haze is 3.0% or more, The vinylidene chloride copolymer contains 1.0 to 15% by mass of structural units derived from methacrylonitrile. A blister packaging film comprising:
Citation Information
Patent Citations
Plastic sheet with thermal molding and barrier characteristics
JP1989113242A
Aqueous emulsion composition of vinylidene chloride resin
JP1991033147A
Method for preparing latex from chlorinated vinyl polymer
JP2013100551A
Sheet for pharmaceutical packaging, bottom material for press-through packaging, press-through packaging material, and sheet
JP2022117395A
Water-based latex of vinylidene chloride copolymer
JP2023506844A
Cited By
Water-based PVDC with high thermal stability and preparation method thereof
CN120718381A